St. Trinian's Church, Marown - Harrison, Stephen N. (Ramsey Church Magazine, 1899)
Keywords: st. trinian's

Fearn Abbey, Ross-shire (Scots Magazine, 1899)
Keywords: fearn

Notes on Torre Abbey - Appleton, E. (Transactions of the Exeter Diocesan Architectural Society, 1899)
Keywords: torre

The Whiteabbey in the Parish of Carnmoney, County Antrim - Bigger, Francis Joseph; Fennell, William J. (Ulster journal of archaeology, 1899)
Keywords: whiteabbey

Whithorn Priory - Dalrymple, Hew (Archæological and Historical Collections Relating to Ayrshire & Galloway, 1899)
Keywords: whithorn

Annales de l'abbaye de Saint-Jean ď Amiens - Du Pré, Maurice (Courtin-Hecquet, 1899)
Keywords: amiens

Écrivains, artistes, et savants de l'ordre de Prémontré: Dictionnaire bio-bibliographique - Goovaerts, André Léon (Société belge de librairie, 1899)
Keywords: 📚 premonstratensian (general)

Chapelry of Brainshaugh - Knowles, W.H. (A history of Northumberland, 1899)
Keywords: guyzance

Jandeures, abbaye et domaine - Labourasse, Henri-Adolphe (Impr. de Contant-Laguerre, 1899)
Keywords: jandeures

Notice sur l'abbaye et le domaine de Jandeures - Labourasse, Henri-Adolphe (Mémoires de la Société des lettres, sciences et arts de Bar-le-Duc, 1899)
Keywords: jandeures

Eine ungedruckte Urkunde Erzbischof Ruthards von Mainz vom Jahre 1103. Mitgeteilt nach dem Kopialbuche des Klosters Ilfeld - Meyer, Karl (Zeitschrift des Vereins für Thüringische Geschichte und Altertumskunde, 1899)
Keywords: ilfeld

L'abbaye de Corneux, sa fondation, son histoire pendant le XIIe et le commencement du XIIIe siècle - Morey, Joseph Marie (Roux Gilbert, 1899)
Keywords: corneux

Series abbatum canoniae Lucenae - Peřinka, František Vácslav (Časopis Matice moravské, 1899)
Keywords: louka

Note sur le cartulaire de Braine - Plateau (Bulletin de la Société archéologique de Soissons, 1899)
Keywords: braine

Kurzer Überblick über die Geschichte des Klosters Langwaden - Redlich, Otto Reinhard (Beiträge zur Geschichte des Niederrheins, 1899)
Keywords: langwaden

Graf Ludwig von Arnstein und die Neubegründung des Klosters Münsterdreisen - Schaus, Emil (Nassauische Annalen, 1899)
Keywords: münsterdreisen

Beati Hermanni Joseph, canonici Steinfeldensis, ord. Praemonstratensis, opuscula ex vetustis cod. mss. eruta, olim vulgata a R.D. Joanne Chrys. Van der Sterre - Spilbeeck, Ignace van (Douzfils, 1899)
Keywords: 👤 hermann joseph of steinfeld

Das Frauenkloster Pernegg (Fortsetzung) - Žák, Alfons (Blätter des Vereines für Landeskunde von Niederösterreich, 1899)
Keywords: pernegg

Abbaye de Dilo - Fournier, A. (La Semaine religieuse du diocèse de Sens et Auxerre, 1898)
Keywords: dilo

The Church Bells of Holywood and Kirkmahoe, and the Church and Municipal Bells of Lochmaben, Part One - Barbour, James (Transactions and Journal of Proceedings of the Dumfriesshire and Galloway Natural History and Antiquarian Society, 1898)
Keywords: holywood

Das Stiftungsjahr des Prämonstratenserklosters Schussenried - Beck, Paul A. (Diözesanarchiv von Schwaben, 1898)
Keywords: schussenried

La prévoté de Renissart à Arquennes - Berlière, Ursmer (Annales du Cercle archéologique de Mons, 1898)
Keywords: renissart

Le Catalogus abbatum Floreffiensium de Pierre de Herenthals - Berlière, Ursmer (Compte-rendu des séances de la commission royale d'histoire, 1898)
Keywords: floreffe

Notes sur les manuscrits de l'abbé Hugo d'Étival conservés à Nancy - Berlière, Ursmer (Bulletin de la Commission royale d'Histoire, 1898)
Keywords: 📚 premonstratensian (general)

L'Église de Laval-Dieu (Ardennes) et ses boiseries sculptées - Bouillet, Auguste (Réunion des sociétés des Beaux-Arts des départements à la Sorbonne, 1898)
Keywords: laval dieu

La charte de Divielle - Dubarat, Victor (Études historiques et religieuses du diocèse de Bayonne, 1898)
Keywords: divielle

The Chartulary of Cockersand Abbey of the Premonstratensian Order - Farrer, William (Remains Historical and Literary Connected with the Palatine Counties of Lancaster and Chester, 1898)
Keywords: cockersand

The Chartulary of Cockersand Abbey of the Premonstratensian Order - Farrer, William (Remains Historical and Literary Connected with the Palatine Counties of Lancaster and Chester, 1898)
Keywords: cockersand

The Chartulary of Cockersand Abbey of the Premonstratensian Order - Farrer, William (Remains Historical and Literary Connected with the Palatine Counties of Lancaster and Chester, 1898)
Keywords: cockersand

L'Abbaye Saint-Yved de Braine (Prémontrés) - Gassies, Georges (Bulletin de la Société littéraire et historique de la Brie, 1898)
Keywords: braine

Kirche des ehemaligen Frauenklosters Unterzell bei Würzburg - Henner, Theodor (Altfränkische Bilder, 1898)
Keywords: unterzell

Bijdragen tot de geschiedenis van de Abdij van Mariënweerd - Hoevenaars, Willibrord (Archief voor de geschiedenis van het aartsbisdom Utrecht, 1898)
Keywords: mariënweerd

L'abbaye de Notre-Dame du Perray-Neuf à Précigné, 1189 - 1898 - Ledru, Ambroise (La Province du Maine, 1898)
Keywords: perray-neuf

Titchfield Abbey and Place House - Minns, G.W. (Proceedings of the Hampshire Field Club & Archaeological Society, 1898)
Keywords: titchfield

Kloster Adelberg: seine Kunstschätze, Geschichte und frühere Gestaltung - Müller, Max (Mayer, 1898)
Keywords: adelberg

Klášter Želiv. Cestopisná črta - Petrů, Vácslav (Cyrillo-Methodějská knihtiskárna a nakladatlství V.Kotrba, 1898)
Keywords: želiv

Notice sur l'abbaye d'Humilimont - Reichlen, F. (Revue de La Suisse Catholique, 1898)
Keywords: humilimont

Notice sur l'abbaye d'Humilimont (suite) - Reichlen, F. (Revue de La Suisse Catholique, 1898)
Keywords: humilimont

Das Kloster Weißenau zur Zeit Ludwigs des Baiern - Schneider, Eugen (Württembergische Vierteljahrshefte für Landesgeschichte, 1898)
Keywords: weissenau

La couronne Norbertine, ou, Saints et bienheureux de l'Ordre de Prémontré - Spilbeeck, Ignace van (Société belge de librairie, 1898)
Keywords: 📚 premonstratensian (general)

Le bienheureux Waltman de l'Ordre de Prémontré, premier abbé de Saint-Michel, à Anvers : notice biographique et iconographique - Spilbeeck, Ignace van (Bulletin de l'Académie royale d'Archéologie, 1898)
Keywords: antwerp

Les armoiries de l'abbaye de Beaurepart de l'ordre de Prémontré - Spilbeeck, Ignace van (Annuaire de l'Académie royale d'archéologie de Belgique, 1898)
Keywords: beaurepart

Vie de Saint Norbert, archevêque de Magdebourg, fondateur de l'ordre de Prémontré : tableaux historiques du XIIe siècle offerts à la jeunesse - Spilbeeck, Ignace van (Société Belge de librairie, 1898)
Keywords: 👤 norbert of xanten

Zwei Steinfelder Urkunden der Kölner Erzbischöfe Konrad und Siegfried - Tille, Armin (Annalen des Historischen Vereins für den Niederrhein, 1898)
Keywords: steinfeld

Les chartes des Mares et de Lametz - Vincent, H. (Revue historique ardennaise, 1898)
Keywords: longwé

Klosterbruck und seine Schicksale im Laufe der Jahrhunderte - Vrbka, Anton (Fournier & Haberle, 1898)
Keywords: louka

Die Gründung des Nonnenklosters Marienbusch bei Treptow a. R. - Wehrmann, Martin (Monatsblätter der Gesellschaft für Pommersche Geschichte und Altertumskunde, 1898)
Keywords: trzebiatów

Kloster Rüti - Rahn, J.R. (Sonntags-Beilage der Allgemeinen Schweizer Zeitung, 1897)
Keywords: rüti

Die Einführung der Kirchen-Reformation in das Kloster Keppel - Achenbach, Heinrich von (Aus des Siegerlandes Vergangenheit, 1897)
Keywords: keppel

Chronique de l'abbaye de Saint-Augustin-lès-Thérouanne - Bonvarlet; Bled (Bulletin de la Société des antiquaires de la Morinie, 1897)
Keywords: saint-augustin-lès-thérouanne

Über den ehemaligen Güterbesitz der Klöster Pöhlde und Elten in friesischen Gebieten - Bunte, Bernhard (Jahrbuch der Gesellschaft für bildende Kunst und vaterländische Altertümer zu Emden, 1897)
Keywords: pöhlde

Drei schlesische Landesheilige: Der heil. Hyacinth, der selige Ceslaus und die selige Bronislawa - Chrząszcz, Jan (G.P. Aderholz Buchhandlung, 1897)
Keywords: 👤 bronislava of kamień

Langwaden - Clemen, Paul (Die Kunstdenkmäler des Kreises Grevenbroich, 1897)
Keywords: langwaden

Analyse du cartulaire de Saint-Jean de la Castelle - Daugé, Césaire (Semaine religieuse d'Aire et de Dax, 1897)
Keywords: la castelle

Notice sur un abrégé en français de la Chronique universelle de Robert de Saint-Marien d'Auxerre, d'après un manuscrit du Musée Condé. - Delisle, Léopold (Bibliothèque de l'École des chartes, 1897)
Keywords: 👤 robert of auxerre

Bijdragen tot de geschiedenis der Premonstranten der Abdij van O.L.V. te Middelburg - Hoevenaars, Willibrord (Bijdragen voor de geschiedenis van het bisdom van Haarlem, 1897)
Keywords: middelburg

Bijdragen tot de geschiedenis van de Abdij van Mariënweerd - Hoevenaars, Willibrord (Archief voor de geschiedenis van het aartsbisdom Utrecht, 1897)
Keywords: mariënweerd

L'abbaye de Notre-Dame du Perray-Neuf à Précigné, 1189 - 1898 - Ledru, Ambroise (La Province du Maine, 1897)
Keywords: perray-neuf

Eglise et chapelle de Fermaincourt - Leménestrel, Charles (Archives du Diocèse de Chartres, 1897)
Keywords: fermaincourt

Ruins and Stones of Holywood Abbey - Martin, J.W. (Transactions and Journal of Proceedings of the Dumfriesshire and Galloway Natural History and Antiquarian Society, 1897)
Keywords: holywood

Das Kloster Ilfeld, nach den Urkunden des Klosters - Meyer, Karl (B. Franke, 1897)
Keywords: ilfeld

Die Reliquien und Reliquiarien der Klosterkirche zu Schussenried - Rueß, Bernhard (Archiv für christliche Kunst: Organ des Rottenburger Diözesan-Kunstvereins, 1897)
Keywords: schussenried

Die Reliquien und Reliquiarien der Klosterkirche zu Schussenried - Rueß, Bernhard (Archiv für christliche Kunst: Organ des Rottenburger Diözesan-Kunstvereins, 1897)
Keywords: schussenried

Die Reliquien und Reliquiarien der Klosterkirche zu Schussenried - Rueß, Bernhard (Archiv für christliche Kunst: Organ des Rottenburger Diözesan-Kunstvereins, 1897)
Keywords: schussenried

Notice sur Phlin (Villingen) - Sanson, Th. (Jahrbuch der Gesellschaft für Lothringische Geschichte, 1897)
Keywords: phlin

Ein Besuch in Knechtsteden: Beschreibung und Geschichte der Abtei - Schmitz, Hermann Josef (Ges. f. Buchdr. Universitäts- und Landesbibliothek, 1897)
Keywords: knechtsteden

Vie du Bienheureux Hroznata, prince de Bohéme : fondateur de l'Abbaye de Tepl et du Monastére de Chotieschow de l'ordre de Prémontré - Spilbeeck, Ignace van (Bibliothèque Norbertine, 1897)
Keywords: 👤 hroznata of bohemia

Excavations at Talley Abbey - Williams, Stephen W. (Archaeologia Cambrensis, 1897)
Keywords: talley

Das Frauenkloster Pernegg - Žák, Alfons (Blätter des Vereines für Landeskunde von Niederösterreich, 1897)
Keywords: pernegg

Die Prämonstratenser-Abtei Rüti - Zeller-Werdmüller, H. (Mitteilungen der Antiquarischen Gesellschaft in Zürich, 1897)
Keywords: rüti

Une excursion à Authon, Saint-Arnoult, Montoire et Saint-Georges-des-Bois - de Saint-Venant, R. (Bulletin de la Société Archéologique du Vendômois, 1896)
Keywords: l'étoile

Notizen die Burg, das Kloster und Amt und die Stadt Jerichow - Eiteljörge, Albert (J. Stephan Druck und Verlag, 1896)
Keywords: jerichow

Notice sur l'abbaye de Longwé, canton du Chesne - Haizeaux, R.C. (s.n., 1896)
Keywords: longwé

Bijdragen tot de geschiedenis van de Abdij van Mariënweerd - Hoevenaars, Willibrord (Archief voor de geschiedenis van het aartsbisdom Utrecht, 1896)
Keywords: mariënweerd

Résumé des documents relatifs à un procès entre le chapitre de Jargeau et le prieuré du Gué-de-l'Orme - Jarry, Louis (Bulletin de la Société archéologique et historique de l'Orléanais, 1896)
Keywords: gué de l'orme

Sceau-matrice du couvent 'Het besloten Hof' à Herenthals - Jonghe, Beaudouin de (Bulletin de l'Académie d'archéologie de Belgique, 1896)
Keywords: herentals

Die Zinsheberolle des Praemonstratenserklosters S. Mariae in Ilfeld - Kühlewein, Hugo (Schulprogramm Ilfeld, 1896)
Keywords: ilfeld

Charte du Perray-Neuf - Ledru, Ambroise (La Province du Maine, 1896)
Keywords: perray-neuf

Prieuré de Lion - Liot, Eugène (Lion-sur-Mer, Hermanville, 1896)
Keywords: lion-sur-mer

Przyczynek do wyjaśnienia pierwotnych dziejów klasztoru Norbertanek w Strzelnie - Łukowski, Jan (Roczniki Towarzystwa Przyjaciół Nauk Poznańskiego, 1896)
Keywords: strzelno

Eine Briefsammlung des Propstes Ulrich von Steinfeld aus dem 12. Jahrhundert - Roth, Ferdinand Wilhelm Emil (Zeitschrift des Aachener Geschichtsvereins, 1896)
Keywords: steinfeld

Eine Briefsammlung des XII. Jahrhunderts aus dem Kloster Steinfeld - Roth, Ferdinand Wilhelm Emil (Neues Archiv der Gesellschaft für ältere deutsche Geschichtskunde, 1896)
Keywords: steinfeld

Umbau der katholischen Pfarrkirche in Bedburg - Rüdell, Karl (Zeitschrift für christliche Kunst, 1896)
Keywords: bedburg

Die Baugeschichte der Klosterkirche von Schussenried - Rueß, Bernhard (Archiv für christliche Kunst, 1896)
Keywords: schussenried

Die Baugeschichte der Klosterkirche von Schussenried - Rueß, Bernhard (Archiv für christliche Kunst, 1896)
Keywords: schussenried

Note sur le prieuré de la Couchère - Tournoüer, H. (Bulletin de la Société Historique et Archéologique de l'Orne, 1896)
Keywords: la cochère

Note sur les sculptures attribuées à l'abbaye de Salival - Wiener, Lucien (Journal de la Société d’archéologie lorraine, 1895)
Keywords: salival

Ilbenstadt - Adamy, Rudolf (Provinz Oberhessen: Kreis Friedberg, 1895)
Keywords: ilbenstadt

Abbaye de Clairfontaine - Bercet, Edouard (Bulletin de la Société archéologique de Vervins, 1895)
Keywords: clairfontaine

Dragsmarks kloster - Berg, Wilhelm (Bonnier, 1895)
Keywords: dragsmark

La chronique de Jean de Sivry, prieur de Bonne-Espérance - Berlière, Ursmer (Annales du Cercle archéologique de Mons, 1895)
Keywords: bonne-espérance

An Ancient MS. Account of the Parish of Marown, written by John Christian, Vicar (about 1776), for Thomas Pennant, Antiquary - Christian, John (Yn Lior Manninagh, 1895)
Keywords: marown

Die S. Lucius Kirche zu Chur - Effmann, W. (Zeitschrift für Christliche Kunst, 1895)
Keywords: chur (st luzi)

Die S. Lucius Kirche zu Chur - Effmann, W. (Zeitschrift für Christliche Kunst, 1895)
Keywords: chur (st luzi)

Geschichte Arnsbergs mit einer alten Ansicht von Stadt und Schloss Arnsberg nebst Abtei Wedinghausen - Féaux de Lacroix, Karl (H.R. Stein, 1895)
Keywords: wedinghausen

Souvenirs archéologiques de l'abbaye de Belval - Graffin, Roger (Revue historique ardennaise, 1895)
Keywords: belval

The Praemonstratensian Abbey of S. Mary & S. John Baptist, Eggleston - Hodgson, J.F. (s.n., 1895)
Keywords: egglestone

Bijdragen tot de geschiedenis van de Abdij van Mariënweerd - Hoevenaars, Willibrord (Archief voor de geschiedenis van het aartsbisdom Utrecht, 1895)
Keywords: mariënweerd

Vier oorkonden uit de XII eeuw, de Abdij van Middelburg betreffende - Hoevenaars, Willibrord (Bijdragen voor de geschiedenis van het bisdom van Haarlem, 1895)
Keywords: middelburg

Das Weiherkloster bei Köln - Jost, J.B.D. (Rheinische Geschichtsblätter, 1895)
Keywords: cologne (weiher)

Dva staré kostely v dekanátu Svitavském na Moravě: Hřbitovní kostel sv. Jiljí ve Svitavech - Kašpar, Josef (Method: časopis věnovany uměni křestanskému, 1895)
Keywords: svitavy

Kdo byl prvním biskupem Litomyšlským? - Konečný, Bohumil V. (Český časopis historický, 1895)
Keywords: litomyšl

Die Geschichte der Königlichen Domäne Manzell und im Zusammenhange damit die Geschichte des Klosters Weißenau - Rief, Friedrich Adolf (Schriften des Vereins für Geschichte des Bodensees und seiner Umgebung, 1895)
Keywords: weissenau

Das Weihefest der Klosterkirche zu Mildenfurth - Schmidt, Berthold (Zeitschrift des Vereins für Thüringische Geschichte und Altertumskunde, 1895)
Keywords: mildenfurth

Die Klosterfrau Katharine Gräfin zu Württemberg - Schneider, Eugen (Literarische Beilagen des Staatsanzeigers für Württemberg, 1895)
Keywords: lauffen

Die Wiltener Gründungssage - Seemüller, Joseph (Zeitschrift des Ferdinandeums, 1895)
Keywords: wilten

Petites fleurs de la vie du bienheureux Herman-Joseph de l'Ordre de Prémontré, offertes aux enfants de Marie - Spilbeeck, Ignace van (Duculot-Roulin, 1895)
Keywords: 👤 hermann joseph of steinfeld

Vie du bienheureux Frédéric de Hallum: fondateur de l'Abbaye du Jardin de Marie de l'Ordre de Prémontré - Spilbeeck, Ignace van (Bibliothèque Norbertine, 1895)
Keywords: mariëngaarde

Das Kloster Gerlachsheim im Taubergrund - Stengele, Benvenut (Diözesan-Archiv von Schwaben: Organ für Geschichte, Altertumskunde, Kunst und Kultur der Diözese Rottenburg und der angrenzenden Gebiete, 1895)
Keywords: gerlachsheim

Das große Abteiwappen des Prämonstratenserklosters Weissenau - Busl, Karl Anton (Diözesanarchiv von Schwaben, 1894)
Keywords: weissenau

De Grafzerk van Petrus van Zuyren, Abt van Mariënweerd (Archief voor de geschiedenis van het aartsbisdom Utrecht, 1894)
Keywords: mariënweerd

Geschiedkundige bijdragen betreffende het Norbertinessen klooster van St. Catharinadal - Aura, V. van der (Van Langenhuysen, 1894)
Keywords: sint-catharinadal

Gr.-Garde - Böttger, Ludwig (Die Bau- und Kunstdenkmäler des Regierungs-Bezirks Köslin, 1894)
Keywords: gardna wielka

Mitteilung über wiederaufgefundene Urkunden aus den Klöstern Bebenhausen, Adelberg und Pfullingen - Busl, Karl Anton (Württembergische Vierteljahrshefte für Landesgeschichte, 1894)
Keywords: adelberg; bebenhausen

Neues zur Baugeschichte der Prämonstratenser-Abtei Weissenau und ihrer Kirche - Busl, Karl Anton (Archiv für christliche Kunst, 1894)
Keywords: weissenau

Iets uit het leven van sommige Abten van het Klooster Mariëngaard onder Hallum - Cannegieter, Dominicus (Friesche Volksalmanak, 1894)
Keywords: mariëngaarde

The seal of the priory of Whithorn - Dalrymple, Hew (Archæological and Historical Collections Relating to Ayrshire & Galloway, 1894)
Keywords: whithorn

Documents sur N.-D. de Sarrance (1343 - XIXe siècle) - Dubarat, Victor-Marie (Mélanges de bibliographie et d'histoire locale, 1894)
Keywords: sarrance

De Stichtingsoorkonde van Mariënweerd - Elsen, Gerlacus van der (Archief voor de geschiedenis van het aartsbisdom Utrecht, 1894)
Keywords: mariënweerd

Die Bau- und Kunstdenkmale des Klosters Steingaden - Hager, Georg (Oberbayerisches Archiv, 1894)
Keywords: steingaden

Bijdragen tot de geschiedenis van de Abdij van Mariënweerd - Hoevenaars, Willibrord (Archief voor de geschiedenis van het aartsbisdom Utrecht, 1894)
Keywords: mariënweerd

Briefwisseling over het aankoopen van de overblijfselen van het Mariënweerdsch Archief - Hoevenaars, Willibrord (Archief voor de geschiedenis van het aartsbisdom Utrecht, 1894)
Keywords: mariënweerd

Eenige aanmerkingen op hetgeen de Zeereerw. hooggel. heer Jos. Habets, in het IIe en IIIe deel van zijne "Geschiedenis van het Bisdom Roermond" heeft medegedeeld omtrent de Abdij van Mariënweerd - Hoevenaars, Willibrord (Archief voor de geschiedenis van het aartsbisdom Utrecht, 1894)
Keywords: mariënweerd

Blanchland - Johnson, Anthony (Archaeologia Aeliana, 1894)
Keywords: blanchland

Urkundliches zur Geschichte des Prämonstratenserinnen-klosters Schäftersheim 1155-1437 - Kerler, Dietrich (Württembergisch Franken: Jahrbuch des Historischen Vereins für Württembergisch Franken, 1894)
Keywords: schäftersheim

A contribution to the history of the Premonstratensian Abbey of Talley - Owen, Edward (Archaeologia Cambrensis, 1894)
Keywords: talley

Inventaire sommaire des chartes de l'abbaye de Chartreuve - Pellot, P. (Revue de Champagne et de Brie, 1894)
Keywords: chartreuve

La Grange de Juliac - Romieu, Maurice (Histoire de la vicomté de Juliac, 1894)
Keywords: lagrange

Die Bauthätigkeit der ehemaligen Prämonstratenser-Abtei Allerheiligen auf dem Schwarzwalde - Schmitt, Franz Jakob (Repertorium für Kunstwissenschaft, 1894)
Keywords: allerheiligen

Das Traditionsbuch und das älteste Einkünfte-Verzeichnis des Klosters Ursberg - Schröder, Alfred (Jahresbericht des Historischen Vereins Dillingen, 1894)
Keywords: ursberg

Das ehemalige Prämonstratenser-Frauenkloster Lochgarten bei Mergentheim - Stengele, Benvenut (Diözesan-Archiv von Schwaben: Organ für Geschichte, Altertumskunde, Kunst und Kultur der Diözese Rottenburg und der angrenzenden Gebiete, 1894)
Keywords: lochgarten

Die Prämonstratenser-Abtei Rüti. Beitrag zur Heimatkunde - Zuppinger, Johann Conrad (Verlag der Lesegesellschaft, 1894)
Keywords: rüti

A contribution to the history of the Premonstratensian Abbey of Talley - Owen, Edward (Archaeologia Cambrensis, 1893)
Keywords: talley

Eine Handschrift der größeren Vita des Gotfried von Kappenberg - Roth, Ferdinand Wilhelm Emil (Korrespondenzblatt des Gesamtvereins der Deutschen Geschichts- und Alterthums-Vereine, 1893)
Keywords: cappenberg

A contribution to the history of the Premonstratensian Abbey of Talley - Owen, Edward (Archaeologia Cambrensis, 1893)
Keywords: talley

A contribution to the history of the Premonstratensian Abbey of Talley - Owen, Edward (Archaeologia Cambrensis, 1893)
Keywords: talley

Die frühere Kloster- und jetzige Pfarrkirche zu Schussenried - Beck, Paul (Diözesanarchiv von Schwaben, 1893)
Keywords: schussenried

L'ancien monastere des Norbertines de Rivreulle - Berlière, Ursmer (Messager des Sciences historiques de Belgique, 1893)
Keywords: rivreulle

Le culte de Notre-Dame de Sarrance, dans l'ancien diocèse d'Auch - Breuils, A. (Études historiques et religieuses du diocèse de Bayonne, 1893)
Keywords: sarrance

Stoppenberg - Clemen, Paul (Die Kunstdenkmäler der Stadt und des Kreises Essen, 1893)
Keywords: stoppenberg

Blanchland - Featherstonehaugh, Walker (Proceedings of the Society of Antiquaries of Newcastle-upon-Tyne, 1893)
Keywords: blanchland

Die bemalten Holzreliefs im Kreuzgang der Stiftskirche zu Griffental - Hann, Franz Gustaf (Carinthia I : Mittheilungen des Geschichtsvereins für Kärnten, 1893)
Keywords: griffen

Versuch der Prämonstratenser, Ilfeld wieder zu besetzen - Jacobs, Eduard (Zeitschrift des Harzvereins für Geschichte und Alterthumskunde, 1893)
Keywords: ilfeld

Deux documents du XIIe siècle concernant le chapitre de Walcourt et l'abbaye de Bonne Espérance - Lahaye, L. (Analectes pour servir à l'Histoire ecclésiastique de la Belgique, 1893)
Keywords: bonne-espérance

S. Bonifazio e S. Alessio sull'Aventino - Lugari, Giovanni Baptiste (Dissertazioni della Pontificia Accademia romana di archeologia, 1893)
Keywords: rome

A contribution to the history of the Premonstratensian Abbey of Talley - Owen, Edward (Archaeologia Cambrensis, 1893)
Keywords: talley

A contribution to the history of the Premonstratensian Abbey of Talley - Owen, Edward (Archaeologia Cambrensis, 1893)
Keywords: talley

Documents relatifs à l'abbaye norbertine d'Heylissem - Reusens, E. (Analectes pour servir à l'histoire ecclésiastique de la Belgique, 1893)
Keywords: heylissem

Le bienheureux Siard, Vde Abbé de Mariengaarde, (Jardin de Marie) de l'ordre de Prémontré - Spilbeeck, Ignace van (Bibliothèque Norbertine, 1893)
Keywords: mariëngaarde

Festschrift zum siebenhundertjährigen Jubiläum der Gründung des Praemonstratenser-Stiftes Tepl - Stift Tepl (Selbtsverlag, 1893)
Keywords: teplá

Zpráva o pramenech dějin kláštera Hradišťského u Olomouce (až do r. 1300) - Teige, Josef (Věstník Královské české společnosti nauk. Třída filosoficko - historicko - filologická, 1893)
Nachrichten über die Quellen zur Geschichte des Klosters Hradisch bei Olmütz
Keywords: hradisko

Das Frauenkloster Himmelspforte in Wien - Žák, Alfons (St. Norbertus Blatt: Zeitschrift zür Förderung katholischen Lebens, zugleich Organ der eucharistischen und charitativen Vereine, Bruderschaften und Werke in Oesterreich, 1893)
Keywords: himmelspforte (austria)

Excavations at Talley Abbey, Carmarthenshire - Williams, Stephen W. (Archaeologia Cambrensis, 1892)
Keywords: talley

Un sanctuaire vénéré au pays lorrain (Notre Dame de Benoite-Vaux) - Bar, E. de (Impr. de l'Oeuvre de Saint Paul, 1892)
Keywords: benoite-vaux

Histoire de Floreffe de l'ordre de Prémontré - Barbier, Victor (Imprimérie Douxfils, 1892)
Keywords: floreffe

Histoire de Floreffe de l'ordre de Prémontré - Barbier, Victor (Imprimérie Douxfils, 1892)
Keywords: floreffe

Philippe de Harvengt, abbé de Bonne-Espérance - Berlière, Ursmer (Revue bénédictine, 1892)
Keywords: bonne-espérance; 👤 philip of harvengt

Documents historiques sur la châtellenie de Vaucouleurs. Premier fascicule, Ermitage Saint-Nicolas-de-Septfonds - Chévelle, Casimir (Impr. E. Munier, 1892)
Keywords: septfonds

Wesel: Prämonstratenserkloster Averdorp - Clemen, Paul (Die Kunstdenkmäler des Kreises Rees, 1892)
Keywords: oberndorf

Histoire du village de Bucilly et de son abbaye - Desmasures, Alfred (Impr. du "Nord de la Thiérache", 1892)
Keywords: bucilly

Le monastère de la Chapelle-aux-Planches - Didier, C. (Mémoires de la Société des lettres, des sciences, des arts, de l'agriculture et de l'industrie de Saint-Dizier, 1892)
Keywords: chapelle aux planches

De abten van Mariënweerd - Hoevenaars, Willibrord (Archief voor de geschiedenis van het aartsbisdom Utrecht, 1892)
Keywords: mariënweerd

De proostdij van Maarsbergen - Hoevenaars, Willibrord (Archief voor de geschiedenis van het aartsbisdom Utrecht, 1892)
Keywords: maarsbergen

Chronique de Notre-Dame de Sarrance dans la vallée d'Aspe en Béarn - Menjoulet, A. (La Cour d'honneur de Marie, 1892)
Keywords: sarrance

Encaustic Tiles at Dureford Abbey and Selborne Priory - Phillips, Charles T. (Sussex Archæological Collections, 1892)
Keywords: durford

Urkundenbuch der Vögte von Weida, Gera und Plauen, sowie ihrer Hausklöster Mildenfurth Cronschwitz, Weida und z.h. Kreuz bei Saalburg - Schmidt, Berthold (Thüringische Geschichtsquellen, 1892)
Keywords: mildenfurth

Das Kloster Bellelay - Schwab, S. (Berner Taschenbuch, 1892)
Keywords: bellelay

Die Marienkirche auf dem Harlungerberg bei Brandenburg - Sello, Georg (Forschungen zur brandenburgischen und preußischen Geschichte, 1892)
Keywords: brandenburg:st marien

Le bienheureux Godefroid, comte de Cappenberg - Spilbeeck, Ignace van (Bibliothèque Norbertine, 1892)
Keywords: cappenberg

Une famille modèle: la bienheureuse Hildegonde, Comtesse de Meer, et ses enfants: le B. Herman et la B. Hadwige, de l'ordre de Prémontré - Spilbeeck, Ignace van (Bibliothèque Norbertine, 1892)
Keywords: 📚 premonstratensian (general)

Het Herentalsch klooster Onzer-Lieve-Vrouwen Besloten-hof der Orde van Premonstreit heden Sint-Josephsdal der Franciskaner Penitentinnen - Spilbeeck, Waltmann van (Drukkerij Compiet, 1892)
Keywords: herentals

Das Kloster Zuckau, die Klosterprobstei und deren neueste Reparaturbauten - Stenzel, Johann (Lehmann, 1892)
Keywords: żukowo

Vestra Tomarps kyrka i Skåne - Tynell, Lars (Kungl. Vitterhets Historie och Antiqvitets Akademiens månadsblad, 1892)
Keywords: tommarp

Abbaye saint Yves alias Yved de Braine - souvenirs Soissonnais-Bretons - Wolbock, de (Bulletin archéologique de l'Association Bretonne publié par la class d'archéologie, 1892)
Keywords: braine

Egglestone Abbey (Monthly Chronicle of North-country Lore and Legend, 1891)
Keywords: egglestone

Kloster Leitzkau - Schütz, H. (Der Bär, 1891)
Keywords: leitzkau

Kloster Leitzkau - Schütz, H. (Der Bär, 1891)
Keywords: leitzkau

Der Kirchenschatz der Klosterkirche zu Schussenried - Beck, Paul (Archiv für christliche Kunst, 1891)
Keywords: schussenried

Holywood Abbey - Black, George F. (Transactions and Journal of Proceedings of the Dumfriesshire and Galloway Natural History and Antiquarian Society, 1891)
Keywords: holywood

Chroniques de Notre-Dame de Sarrance - Dubarat, Victor-Marie (Le Bulletin catholique du diocèse de Bayonne : annales religieuses du Béarn et du Pays basque, 1891)
Keywords: sarrance

Notice sur l'abbaye de Joyenval - Dutilleux, Adolphe (Cerf et fils, 1891)
Keywords: joyenval

Abbaye de Notre-Dame de la Capelle - Larrondo, Henri-Dominique (Une Commune rurale avant la Révolution ou Histoire de la baronnie de Merville : pays de Guyenne, sénéchaussée et diocèse de Toulouse, 1891)
Keywords: la capelle

Zum Chronicon Urspergense - Lindner, Theodor (Neues Archiv der Gesellschaft für Ältere Deutsche Geschichtskunde zur Beförderung einer Gesamtausgabe der Quellenschriften deutscher Geschichten des Mittelalters, 1891)
Keywords: ursberg

Das Prämonstratenserkloster Windberg im bayerischen Wald - Neureuther, Eugen Napoleon (Schulprogramm Straubing, 1891)
Keywords: windberg

Paměti Kláštera v Louňovicích - Sedlácek, August (1891)
Keywords: louňovice

Zur Gründungsgeschichte der Prämonstratenserstifte Geras und Pernegg - Žák, Alfons (Blätter des Vereines für Landeskunde von Niederösterreich, 1891)
Keywords: geras; pernegg

Alnwick Abbey - W., S. (Monthly chronicle of north-country lore and legend, 1890)
Keywords: alnwick

Het klooster "Jerusalem" of het Gerkesklooster: eene bydrage tot de geschiedenis der kloosters in Friesland - Andreae, Arnoldus Johannes (J. Engelsma Mebius, 1890)
Keywords: gerkesklooster

Abbaye de Leffe - Berlière, Ursmer (Monasticon Belge, 1890)
Keywords: leffe

Prieuré de Vérofle - Berlière, Ursmer (Monasticon Belge, 1890)
Keywords: vérofle

Aubri-le-Panthou, son Eglise, son Château et ses Seigneurs - Dallet, A. (Bulletin de la Société Historique et Archéologique de l'Orne, 1890)
Keywords: aubry-le-panthou

Confirmationes statutorum et libertatum ordinis Premonstratensis - Douais, Marie-Jean-Célestin (Annales du Midi, 1890)
Keywords: la capelle; ⚖️ chapters and statutes

L'Aquitaine historique et monumentale. La ville de Hastingues et l'abbaye d'Arthous - Dufourcet, Eugène; Taillebois, Emile; Camiade, Georges (Bulletin de la Société de Borda, 1890)
Keywords: arthous

L'abbaye de Joyenval au diocèse de Chartres - Dutilleux, Adolphe (Mémoires de la Société historique et archéologique de l'arrondissement de Pontoise et du Vexin, 1890)
Keywords: joyenval

Das Kloster Allerheiligen - Fecht, Karl Gustav (Macklot, 1890)
Keywords: allerheiligen

Cartularium der abdij Mariënweerd - Fremery, James de (M. Nijhoff, 1890)
Keywords: mariënweerd

Notice sur l'abbaye de Postel de l'ordre de prémontré - Goffaerts, Camille (Impr. Fonteyn, 1890)
Keywords: postel

Die Ursperger Chronik und ihr Verfasser - Gronau, Georg (Buchdruckerei von A. Seydel, 1890)
Keywords: ursberg

De proostdij van Maarsbergen - Hoevenaars, Willibrord (Archief voor de geschiedenis van het aartsbisdom Utrecht, 1890)
Keywords: maarsbergen

Zekere proostdij te Haarlem, Sint-Antoniusboomgaard genoemd en aan de abdij van Mariënweerd onderhoorig, komt aan het Sint-Elisabethsgasthuis dier stad (1542-1544) - Hoevenaars, Willibrord (Archief voor de Geschiedenis van het Aartsbisdom Utrecht, 1890)
Keywords: antoniusboomgaard

Excursion à l'abbaye d'Ardenne (près Caen) de l'ordre des Prémontrés : Autrefois - Aujourd'hui - Liot, Eugène (Henri Delesques, Imprimeur-Éditeur, 1890)
Keywords: ardenne

Donation des Terrage et dime de Vervins par la veuve et les enfants de Thomas de Marle - Mennesson, Eugène (Bulletin de la Société archéologique de Vervins, 1890)
Keywords: prémontré

Bladen uit de geschiedenis van Ninove - Plas, Leo (Boekhandel van Weduwe Jacobs en Zonen, 1890)
Keywords: ninove

Observations at Leiston Abbey (23 June 1890) - St. John Hope, W.J. (Proceedings of the Suffolk Institute of Archaeology, 1890)
Keywords: leiston

Konradsdorf - Wagner, Heinrich (Die Kunstdenkmäler im Großherzogtum Hessen. C: Provinz Oberhessen. Bd. 1: Kreis Büdingen, 1890)
Keywords: konradsdorf

Dale and its abbey, Derbyshire: a short history and guide - Ward, John (Bewley and Roe, 1890)
Keywords: dale

L'abbaye de Belval - Derazey, Albert (Annales de la Société d'émulation du département des Vosges, 1889)
Keywords: belval

L'église et les inscriptions de l'abbaye de Corneux - Gauthier, Jules (Bulletin de la Société d'agriculture lettres sciences et arts du département de la Haute-Saône, 1889)
Keywords: corneux

Abbaye de Licques, ordre de Prémontré, 1078-1311 - Haigneré, Daniel (Cartulaire des établissements religieux du Boulonnais, 1889)
Keywords: licques

Les chartes de Notre-Dame de Licques (1078-1311) - Haigneré, Daniel (Mémoires de la Société académique de l'arrondissement de Boulogne-sur-Mer, 1889)
Keywords: licques

On the Praemonstratensian abbey of St Agatha juxta Richmond - Hope, W. H. St John (Yorkshire Archaeological and Topographical Journal, 1889)
Keywords: easby

On the Premonstratensian Abbey of St. Mary at Alnwick - Hope, William Henry St John (Archaeologia Aeliana, 1889)
Keywords: alnwick

Komunikat o opactwie norbertańskim zwanym w dawnych czasach „de Brzesko” - Łuszczkiewicz, Władysław (Sprawozdania Komisji do Badania Historii Sztuki w Polsce, 1889)
Keywords: brzesko

Erklärung der Mosaik-Bilder in der Pfarrkirche zu Merzig - Reiß, Matthias (Aktien-Buchdruckere, 1889)
Keywords: merzig

Adliges Augustiner-Nonnenkloster zu Niederehe, später Prämonstratenser-Mönchskloster - Schorn, Carl (Eiflia Sacra oder Geschichte der Klöster und geistlichen Stiftungen der Eifel. Zugleich Fortsetzung resp. Schluß der Eiflia, 1889)
Keywords: niederehe

Adliges Prämonstratenser-Nonnenkloster Wenau - Schorn, Carl (Eiflia Sacra oder Geschichte der Klöster und geistlichen Stiftungen der Eifel. Zugleich Fortsetzung resp. Schluß der Eiflia, 1889)
Keywords: wenau

Prämonstratenserkloster Reichenstein - Schorn, Carl (Eiflia Sacra oder Geschichte der Klöster und geistlichen Stiftungen der Eifel. Zugleich Fortsetzung resp. Schluß der Eiflia, 1889)
Keywords: reichenstein

Vie de la bienheureuse Oda de l'Ordre de Prémontré, le Lis de Bonne-espérance - Spilbeeck, Ignace van (Bibliothèque Norbertine, 1889)
Keywords: 👤 oda of rivreulle

The Premonstratensian Abbey of St Mary Magdalene at Shap, Westmorland - Weston, G.F.; St John Hope, W.H. (Transactions of the Cumberland and Westmorland Antiquarian and Archaeological Society, 1889)
Keywords: shap

Mariëngaarde, een vrouwenklooster binnen de stad Monnikendam - Wüstenhoff, D. J. M. (Archief voor Nederlandsche kerkgeschiedenis, 1889)
Keywords: mariëngaarde

Dryburgh Abbey: Its Monks and Its Lords (Printed for the Proprietor by Craighead Bros., 1888)
Keywords: dryburgh

Fragmenta necrologii Adelbergensis - Baumann, Franz Ludwig (Dioeceses Augustensis, Constantiensis, Curiensis, 1888)
Keywords: adelberg

Kunst en wetenschap in de friesche kloosters Rozenkamp en Bloemhof - Beissel, Stephan (De Dietsche warande. Tijdschrift voor kunst en Zedegeschiedenis, 1888)
Keywords: bloemhof

Un privilège inédit du pape Innocent III publié d'après le cartulaire de l'abbaye de Silly - Blin, J.-B.-N. (Impr. Seguin Frères, 1888)
Keywords: silly

L'Abbaye du Val-Chrétien - Corlieu, Auguste (Annales de la Société historique et archéologique de Château-Thierry, 1888)
Keywords: val-chrétien

Notice historique sur Vascœuil et le prieuré de l'Île-Dieu - Duchemin, Pierre Polovic (Impr. de l'Écho Républicain, 1888)
Keywords: isle-dieu

Bijdragen tot de geschiedenis van de abdij te Middelburg en van het nonnen-klooster te Zoetendaal - Eisen, G. van der (Bijdragen voor de geschiedenis van het bisdom van Haarlem, 1888)
Keywords: middelburg; serooskerke

Ilbenstadt in Oberhessen. Prämonstratenser - Falk, Franz (Zeitschrift für christliche Kunst, 1888)
Keywords: ilbenstadt

Bellelay und seine Geschichte - Frank (Vom Jura zum Schwarzwald: Geschichte, Sage, Land und Leute, 1888)
Keywords: bellelay

De abten van Mariënweerd: de "Nomina abbatum", enz. - Fremery, James de (M. Nijhoff, 1888)
Keywords: mariënweerd

Zur älteren geschichtlichen Überlieferung des Klosters Cappenberg - Ilgen, Theodor (Zeitschrift für vaterländische Geschichte und Altertumskunde (Westfalen), 1888)
Keywords: cappenberg

Liber mortuorum monasterii S. Vincentii Vratislaveiensis, Ord. Praem - Kętrzyński, Wojciech (Monumenta Poloniae historica, 1888)
Keywords: wrocław

Liber mortuorum monasterii Strzelnensis, Ord. Praem. - Kętrzyński, Wojciech (Monumenta Poloniae historica, 1888)
Keywords: strzelno

Notice sur l'abbaye Chaumont-Porcien - Lannois, A. (G. Bauvarlet, 1888)
Keywords: chaumont-porcien

Note sur les chartriers de Val-Secret et d’Essômes - Poquet, Alexandre (Annales de la Société historique et archéologique de Château-Thierry, 1888)
Keywords: val-secret

Rapport sur l'Histoire de St-Just-en-Chaussée, par M. l'abbé Pihan - Poujol de Fréchencourt, Fernand (Bulletin de la Société des antiquaires de Picardie, 1888)
Keywords: saint-just-en-chaussée

Zwei Wedinghauser Urkunden - Schmidt, Adolf (Neues Archiv der Gesellschaft für Ältere deutsche Geschichtskunde, 1888)
Keywords: wedinghausen

Adliges Prämonstratenser-Nonnenkloster Engelport - Schorn, Karl (Eiflia Sacra oder Geschichte der Klöster und geistlichen Stiftungen der Eifel. Zugleich Fortsetzung resp. Schluß der Eiflia, 1888)
Keywords: engelport

Prämonstratenserkloster Füssenich - Schorn, Karl (Eiflia Sacra oder Geschichte der Klöster und geistlichen Stiftungen der Eifel. Zugleich Fortsetzung resp. Schluß der Eiflia, 1888)
Keywords: füssenich

De abdij van Tongerloo: geschiedkundige navorschingen - Spilbeeck, Waltmann van (Taymans-Nezy, 1888)
Keywords: tongerlo

O zalozeniu i uposazeniu strzelińskiego klasztoru - Ulanowski, Bolesław (Archiwum komisyi historycznej Akademii Umiejetnosci w Krakowie, 1888)
Keywords: strzelno

Strzelno i jego najdawniejsze przywileje - Ulanowski, Bolesław (Archiwum Komisyi Historycznej, 1888)
Keywords: strzelno

Het Refugiehuis der abdij postel te 's Hertogenbosch - Welvaarts, Theodorus Ignatius (Werken van het Provinciaal Genootschap van Kunsten en Wetenschappen in Noordbrabant. Nieuwe reeks, 1888)
Keywords: 's hertogenbosch

Some Notes on the Abbey of Holywood and on the Welshes of Colliestoun and Craigenputtock - Aitken, John Carlyle (Transactions and Journal of Proceedings of the Dumfriesshire and Galloway Natural History and Antiquarian Society, 1887)
Keywords: holywood

Kloster Bruderhartmannszell. Übersichtliche Geschichte des Klosters - Bossert, Gustav (Württembergische Vierteljahrshefte für Landesgeschichte, 1887)
Keywords: bruderhartmannzell

L’abbaye de Val-Secret - Corlieu, Auguste (Annales de la Société historique et archéologique de Château-Thierry, 1887)
Keywords: val-secret

Description sommaire du cartulaire de l'abbaye de Saint-Feuillien, au Rœulx - Devillers, Léopold (Annales du Cercle archéologique de Mons, 1887)
Keywords: rœulx

Das Kloster Reichenstein von seiner Gründung bis zu seinem Untergange - Forst, H. (Jahrbuch des Düsseldorfer Geschichtsvereins, 1887)
Keywords: reichenstein

Eene kleine bijdrage uit het archief van Berne tot de geschiedenis der abdij van Mariënweerd - Hoevenaars, Willibrord (Archief voor de geschiedenis van het aartsbisdom Utrecht, 1887)
Keywords: berne; mariënweerd

Het Premonstratenser-Nonnenklooster van Zennewijnen, of een aantal tot hiertoe onuitgegeven oorkonden van dit klooster - Hoevenaars, Willibrord (Archief voor de geschiedenis van het Aartsbisdom Utrecht, 1887)
Keywords: zennewijnen

On the Premonstratensian Abbey of St. Mary Alnwick, Northumberland - Hope, William Henry St John (The archaeological journal, 1887)
Keywords: alnwick

Catalogus canonicorum regularium ordinis Praemonstratensis S. P. Norberti canoniae Plagensis vulgo Schlaegl in Austria Sup. ab armo fundationis 1218 usque as praesens tempus - Pröll, Laurenz (Canoia Plagensis, 1887)
Keywords: schlägl

Les abbayes du département de l'Aube: Abbayes de Bar-sur-Aube (Saint-Nicolas), Basse-Fontaine et Beaulieu. Additions et corrections au Gallia Christiana, Tomes IV et XII - Roserot, Alphonse (Bulletin historique et philologique du Comité des travaux historiques et scientifiques, 1887)
Keywords: basse fontaine; beaulieu

Die Michaels-Basilika auf dem heiligen Berg bei Heidelberg. Eine baugeschichtliche Studie - Schleuning, Wilhelm (1887)
Keywords: michaelskloster

Die Wartenberg'schen Wirren im Prämonstratenserkloster Schussenried - Beck, Paul (Diözesanarchiv von Schwaben, 1886)
Keywords: schussenried

Die Wartenberg'schen Wirren im Prämonstratenserkloster Schussenried - Beck, Paul (Diözesanarchiv von Schwaben, 1886)
Keywords: schussenried

Le Bienheureux Ornifrius, abbé de Dilo (1er avril) (La Cour d'honneur de Marie, 1886)
Keywords: dilo

Heddon-on-the-Wall: The Church and Parish - Bates, Cadwallader J. (Archaeologia Aeliana, 1886)
Keywords: heddon-on-the-wall

Recherches historiques sur la commune de Favières-en-Brie, Seine-et-Marne, ses antiquités, ses seigneuries, ses fiefs, l'abbaye d'Hermières et le prieuré de Saint-Ouen, etc., et quelques aperçus sous Tournan - Besoul, Louis-Adolphe (A. Drosne, 1886)
Keywords: favières; hermières

Bibliographie: Du prieuré de Gérigny (Ardennes), ordre de Prémontré, 1130-1789, par M. l’Abbé Carré - Daras, L. (La Cour d'honneur de Marie, 1886)
Keywords: gérigny

Le Bienheureux Berthold, abbé de Saint-Marien d'Auxerre (3 avril) - Daras, L. (La Cour d'honneur de Marie, 1886)
Keywords: auxerre (st-marien)

Les Fondations Norbertines - Daras, L. (La Cour d'honneur de Marie, 1886)
Keywords: 📚 premonstratensian (general)

Mots celtiques dans les chartes de Beauport - Dottin, G. (Revue Celtique, 1886)
Keywords: beauport

Annales breves Ordinis Praemonstratensis, seu Annalium et rerum ejusdem Ordinis fusiorum ab ejus fundatione ad annum 1645 aliquando vulgandorum epitome - Du Pré, Mauritius (Douxfils, 1886)
Keywords: 📚 premonstratensian (general)

The life of S. Norbert, founder of the Order of Prémontré, Archbishop of Magdeburg - Geudens, Martin (R. Washbourne, 1886)
Keywords: 👤 norbert of xanten

La Bienheureuse Adélaïde de Grandpré - Guelliot, O. (La Cour d'honneur de Marie, 1886)
Keywords: crécy

Het Premonstratenser-Nonnenklooster van Zennewijnen, of een aantal tot hiertoe onuitgegeven oorkonden van dit klooster - Hoevenaars, Willibrord (Archief voor de geschiedenis van het Aartsbisdom Utrecht, 1886)
Keywords: zennewijnen

Note on the Mediaeval Paving Tiles from Langdon Abbey - Hope, William Henry St John (Proceedings of the Society of Antiquaries of London, 1886)
Keywords: langdon

Über die älteste tschechische Urkunde des Stiftes Schlägl - Klimesch, Johann Matthäus (Mitteilungen des Vereines für Geschichte der Deutschen in Böhmen, 1886)
Keywords: schlägl

Zur Geschichte des Klosters Dünnwald, Regesten - Korth, Leonard (Zeitschrift des Bergischen Geschichtsvereins, 1886)
Keywords: dünnwald

Mitteilungen zur Geschichte des Klosters und der Klosterschule zu Ilfeld - Kühlewein, Hugo (Jahresbericht, 1886)
Keywords: ilfeld

Histoire de saint Norbert, fondateur de l'ordre de Prémontré et archevêque de Magdebourg : d'après les manuscrits et les documents originaux - Madelaine, Godefroid (Impr. de Desclée, de Brouwer et Cie, 1886)
Keywords: 👤 norbert of xanten

Burchardus van Wychen en de abdij van Berne - Mes, Gomarius Emmanuël (Volksalmanak voor Nederlandsche Katholieken, 1886)
Keywords: berne

Une copie non datée de l'acte de fondation de l'abbaye de Combelongue - Pradet, A. (La Cour d'honneur de Marie, 1886)
Keywords: combelongue

Cockersand Abbey - Roper, William O. (Transactions of the Lancashire and Cheshire Antiquarian Society, 1886)
Keywords: cockersand

Zacharias Chrysopolitanus und sein Kommentar zur Evangelienharmonie. Eine exegetisch-historische Studie - Schmid, Otto (Theologische Quartalschrift, 1886)
Keywords: 👤 zachary of besançon

Das Prämonstratenserstift S. Maria zu Grifenthal in Unterkärnten - Schroll, Beda (Archiv für vaterländische geschichte und topographie, 1886)
Keywords: griffen

Vie du B. Aldéric, prince de la maison de France, frère convers au couvent de Fuessenich - Spilbeeck, Ignace van (Bibliothèque Norbertine, 1886)
Keywords: füssenich

Urkundliches zur Geschichte der Klöster Anhalts: Das Mönchskloster Kölbigk - Stenzel, Theodor (Mitteilungen des Vereins für Anhaltische Geschichte und Altertumskunde, 1886)
Keywords: cölbigk

L'abbaye d'Etival: sa bibliothèque, ses manuscrits, ses archives - Benoît, Arthur (Bulletin de la société philomatique vosgienne, 1885)
Keywords: étival

Geschichte des Klosters U.L. Frauen zu Magdeburg - Bormann, Albert; Hertel, Gustav (Verlag von Albert Rathke, 1885)
Keywords: magdeburg

Notes on a mediaeval Grave Cover from Alnwick Abbey - Bruce, John Collingwood (Archaeologia Aeliana, 1885)
Keywords: alnwick

Notice historique sur le prieuré de Gérigny de l'ordre de Prémontré au diocèse de Reims, 1130-1789 - Carré, J. B. E. (P. Michaud, 1885)
Keywords: gérigny

Abbayes et prieurés de l’ordre de Prémontré dans l’Ancienne Belgique - Claessens, P. (Precis Historiques, 1885)
Keywords: 🇧🇪 belgium (general)

Archives de l'Abbaye de Haguenau - Daras, Louis (Annales Norbertines, 1885)
Keywords: haguenau

L'ordre de Prémontré et la civilisation de l'Alsace Lorraine - Daras, Louis (La cour d'honneur de Marie, 1885)
Keywords: 🇫🇷 france (general)

Necrologium Doxanense - Emler, Josef (Sitzungsberichte der Königl. Böhmischen Gesellschaft in Prag / Zprávy o zasedáni Královské Ceské Spolecnosti Nauk v Praze, 1885)
Keywords: doksany

Die Handschriften in den Archiven der Stifter Essen, Rellinghausen und Stoppenberg - Humann, Georg (Rheinisches Archiv. Wegweiser durch die für die Geschichte des Mittel- und Niederrheins wichtigen Handschriften. Tl. 1: Der Niederrhein, 1885)
Keywords: stoppenberg

Das Kloster Dünwald - Korth, Leonard (Annalen des Historischen Vereins für den Niederrhein, 1885)
Keywords: dünnwald

Histoire de Saint-Just-en-Chaussée - Pihan, Louis (Impr. D. Pere, 1885)
Histoire de Saint-Just-en-Chaussée (Oise)... / par M. le chanoine L. Pihan,... -- 1885 -- livre
Keywords: saint-just-en-chaussée

Urkundenbuch der Vögte von Weida, Gera und Plauen, sowie ihrer Hausklöster Mildenfurth Cronschwitz, Weida und z.h. Kreuz bei Saalburg - Schmidt, Berthold (Thüringische Geschichtsquellen, 1885)
Keywords: mildenfurth

Une fleur cachée: La bienheureuse Christine du Christ, religieuse du monastère de Rhetirs - Spilbeeck, Ignace van (Bibliothèque Norbertine, 1885)
Keywords: 👤 christina of hane

Necrologium van het klooster Bethleem te Zwolle - Spilbeeck, Waltmann van (Verslagen en Mededeelingen van de Vereeniging tot Beoefening van Overijsselsch Regt en Geschiedenis, 1885)
Keywords: bartlehiem

Die Zeitstellung der Klosterkirche von Jerichow (Schluss) - Schäfer, Karl (Zentralblatt der Bauverwaltung, 1884)
Keywords: jerichow

Die Zeitstellung der Klosterkirche von Jerichow - Schäfer, Karl (Zentralblatt der Bauverwaltung, 1884)
Keywords: jerichow

Die Klosterkirche von Jerichow (Schluss) - Adler, F. (Zentralblatt der Bauverwaltung, 1884)
Keywords: jerichow

Die Klosterkirche von Jerichow (Fortseztung statt Schluss) - Adler, F. (Zentralblatt der Bauverwaltung, 1884)
Keywords: jerichow

Die Klosterkirche von Jerichow (Fortseztung) - Adler, F. (Zentralblatt der Bauverwaltung, 1884)
Keywords: jerichow

Die Klosterkirche von Jerichow (Fortseztung) - Adler, F. (Zentralblatt der Bauverwaltung, 1884)
Keywords: jerichow

Zur Geschichte des Prämonstratenserklosters und der Kirche Weissenau - Bußl, Karl Anton (Diözesan-Archiv von Schwaben: Organ für Geschichte, Altertumskunde, Kunst und Kultur der Diözese Rottenburg und der angrenzenden Gebiete, 1884)
Keywords: weissenau

Die Klosterkirche von Jerichow - Adler, F. (Zentralblatt der Bauverwaltung, 1884)
Keywords: jerichow

Zur Geschichte des Prämonstratenserklosters und der Kirche Weissenau - Bußl, Karl Anton (Diözesan-Archiv von Schwaben: Organ für Geschichte, Altertumskunde, Kunst und Kultur der Diözese Rottenburg und der angrenzenden Gebiete, 1884)
Keywords: weissenau

Zur Geschichte des Prämonstratenserklosters und der Kirche Weissenau - Bußl, Karl Anton (Diözesan-Archiv von Schwaben: Organ für Geschichte, Altertumskunde, Kunst und Kultur der Diözese Rottenburg und der angrenzenden Gebiete, 1884)
Keywords: weissenau

Zur Geschichte des Prämonstratenserklosters und der Kirche Weissenau - Bußl, Karl Anton (Diözesan-Archiv von Schwaben: Organ für Geschichte, Altertumskunde, Kunst und Kultur der Diözese Rottenburg und der angrenzenden Gebiete, 1884)
Keywords: weissenau

Zur Geschichte des Prämonstratenserklosters und der Kirche Weissenau - Bußl, Karl Anton (Diözesan-Archiv von Schwaben: Organ für Geschichte, Altertumskunde, Kunst und Kultur der Diözese Rottenburg und der angrenzenden Gebiete, 1884)
Keywords: weissenau

Zum steten frommen Andenken an das 700jährige Jubiläum des Prämonstratenser-Reichsstifts Schussenried - Beck, Paul (Diözesan-Archiv von Schwaben: Organ für Geschichte, Altertumskunde, Kunst und Kultur der Diözese Rottenburg und der angrenzenden Gebiete, 1884)
Keywords: schussenried

Zur Geschichte des Prämonstratenserklosters und der Kirche Weissenau - Bußl, Karl Anton (Diözesan-Archiv von Schwaben: Organ für Geschichte, Altertumskunde, Kunst und Kultur der Diözese Rottenburg und der angrenzenden Gebiete, 1884)
Keywords: weissenau

Zur Geschichte des Prämonstratenserklosters und der Kirche Weissenau - Bußl, Karl Anton (Diözesan-Archiv von Schwaben: Organ für Geschichte, Altertumskunde, Kunst und Kultur der Diözese Rottenburg und der angrenzenden Gebiete, 1884)
Keywords: weissenau

Zum steten frommen Andenken an das 700jährige Jubiläum des Prämonstratenser-Reichsstifts Schussenried - Beck, Paul (Diözesan-Archiv von Schwaben: Organ für Geschichte, Altertumskunde, Kunst und Kultur der Diözese Rottenburg und der angrenzenden Gebiete, 1884)
Keywords: schussenried

Zur Geschichte des Prämonstratenserklosters und der Kirche Weissenau - Bußl, Karl Anton (Diözesan-Archiv von Schwaben: Organ für Geschichte, Altertumskunde, Kunst und Kultur der Diözese Rottenburg und der angrenzenden Gebiete, 1884)
Keywords: weissenau

Zur Geschichte des Prämonstratenserklosters und der Kirche Weissenau - Bußl, Karl Anton (Diözesan-Archiv von Schwaben: Organ für Geschichte, Altertumskunde, Kunst und Kultur der Diözese Rottenburg und der angrenzenden Gebiete, 1884)
Keywords: weissenau

L'église de Valprofonde (La Cour d’honneur de Marie, 1884)
Keywords: valprofonde

Het Klooster te Olijfberg en de buitenplaats Fogelsangh-State - Andreae, Arnoldus Johannes (Jaarboekje van den Frieschen adel in verband tot de ridderschap van Friesland, 1884)
Keywords: veenklooster

Monumenta Windbergensia. I. Theil: Traditiones - Braunmüller, B. (Verhandlungen des Historischen Vereins für Niederbayern, 1884)
Keywords: windberg

Zur Geschichte des Prämonstratenserklosters und der Kirche Weissenau - Busl, Karl Anton (Diözesan-Archiv von Schwaben (zugleich Organ für deutsche Kirchengeschichte), 1884)
Keywords: weissenau

Zlomek urbáře kláštera Hradištského - Emler, Josef (Pojednání Král. české společnosti nauk, 1884)
Keywords: hradisko

Esquisse de l'histoire littéraire de l'ordre de Prémontré, suivi d'une nomenclature des écrivains de l'ordre de Prémontré depuis sa fondation jusqu'à nos jours, 1120-1884 - Gonzague, Louis de (Palmé, 1884)
Keywords: 📚 premonstratensian (general)

Święty Norbert i jego zakon : początki norbertańskich klasztorów w cyrkarji polskiej i nieco z ich dziejów - Knapiński, Władysław (1884)
Keywords: 🇵🇱 poland (general)

Zur Geschichte des Klosters Dünnwald im 12. und 13. Jahrhundert - Korth, Leonard (Zeitschrift des Bergischen Geschichtsvereins, 1884)
Keywords: dünnwald

Ludolf, Bischof von Ratzeburg (1236-1250) - Krause, Karl Ernst Hermann (Allgemeine Deutsche Biographie, 1884)
Keywords: 👤 ludolf of ratzeburg

Notice historique sur L'Abbaye de Leffe: avec de nombreuses piéces justificatives et un appendice sur la Paroisse de Leffe - Quinaux, C. J (Godenne, 1884)
Keywords: leffe

Stichting van Buweklooster - Reitsma, J. (Friesche Volksalmanak, 1884)
Keywords: buweklooster

Stichting van Buweklooster, sepulchrum Sanctae Mariae - Reitsma, J. (Friesche Volksalmanak, 1884)
Keywords: speinshart

Geschichte des Klosters Osterhofen-Damenstift - Sittersperger, Johann Nepomuk (Waldbauer, 1884)
Keywords: osterhofen

Das älteste Bücherverzeichnis des Klosters Arnstein - Widmann, Simon (Annalen des Vereins für Nassauische Altertumskunde und Geschichtsforschung, 1884)
Keywords: arnstein

Der 700jährigen Jubiläum des Klosters Schussenried (Schwäbische Kronik, 1883)
Keywords: schussenried

Zum siebenhundertjährigen Jubiläum des Prämonstratenser-Reichsstifts Schussenried - Beck, Paul (Deutsches Volksblatt, 1883)
Keywords: schussenried

Prämonstratenser-Chorherrenstift Selau - Bezděka, Victor (Ein Chorherrenbuch. Geschichte und Beschreibung der bestehenden und Anführung der aufgehobenen Chorherrenstifte: Augustiner und Prämonstratenser in Österreich-Ungarn, Deutschland und der Schweiz, 1883)
Keywords: želiv

De Abdij Bloemhof te Wittewierum in de 13e eeuw - Bottemanne, C.J.M. (De Katholiek. Godsdienstig, Geschied- en Letterkundig Maandschrift, 1883)
Keywords: bloemhof

Die Pramonstratenser-Abtei Tepl - Brunner, Sebastian (Ein Chorherrenbuch. Geschichte und Beschreibung der bestehenden und Anführung der aufgehobenen Chorherrenstifte: Augustiner und Prämonstratenser in Österreich-Ungarn, Deutschland und der Schweiz, 1883)
Keywords: teplá

Die Propstei Csorna - Brunner, Sebastian (Ein Chorherrenbuch. Geschichte und Beschreibung der bestehenden und Anführung der aufgehobenen Chorherrenstifte: Augustiner und Prämonstratenser in Österreich-Ungarn, Deutschland und der Schweiz, 1883)
Keywords: csorna

Das Prämonstratenser-Chorherrenstift Strahov oder Berg Sion in Prag - Čermák, Dominik Karel (Ein Chorherrenbuch. Geschichte und Beschreibung der bestehenden und Anführung der aufgehobenen Chorherrenstifte: Augustiner und Prämonstratenser in Österreich-Ungarn, Deutschland und der Schweiz, 1883)
Keywords: strahov

Obituaire du monastère de St-André de Clermont - Cohendy, M. (Bulletin historique et scientifique de l'Auvergne, 1883)
Keywords: clermont

Urkunden des Klosters Dünnwald 1264-1360 - Crecelius, Wilhelm; Harleß, Woldemar (Zeitschrift des Bergischen Geschichtsvereins, 1883)
Keywords: dünnwald

Un procès entre religieux au XVIIe siècle : la grange de Lannes de Mezin - Faugère-Dubourg, M. (Revue de l'Agenais, 1883)
Keywords: lannes

Die Prämonstratenser Wüstungen Kloster Gummersheim und Propstei Petersberg - Gredy, Heinrich (Geschichte der ehemaligen freien Reichsstadt Odernheim, 1883)
Keywords: gommersheim; petersberg

Le Pèlerinage de la ville de Nancy à Notre-Dame de Benoîte-Vaux en 1642 - Guinet, Macaire (G. Crépin-Leblond, 1883)
Keywords: benoite-vaux

Urkundenbuch des Prämonstratenserklosters Arnstein an der Lahn - Herquet, Karl (Verlag von Chr. Limbarth, 1883)
Keywords: arnstein

On the Premonstratensian Abbey at West Langdon - Hope, William Henry St John (Archaeologia Cantiana, 1883)
Keywords: langdon

Jászó und die mit ihm vereinigten Propsteien Lelesz and Promontor von Grosswardein - Lenner, Julius Ferdinand (Ein Chorherrenbuch. Geschichte und Beschreibung der bestehenden und Anführung der aufgehobenen Chorherrenstifte: Augustiner und Prämonstratenser in Österreich-Ungarn, Deutschland und der Schweiz, 1883)
Keywords: jasov; leles

Histoire de l'abbaye royale de Saint-Jean-de-Falaise, ordre de Prémontrés - Mériel, Amédée (Imprimerie A. Lepage, 1883)
Keywords: falaise

Saint-Just-en-Chaussée, étude historique et archéologique (suite) - Pihan, Louis (Mémoires de la Société Académique d’Archéologie, Sciences et Arts du Département de l’Oise, 1883)
Keywords: saint-just-en-chaussée

Ehemalige Prämonstratenser-Stifte - Pröll, Laurenz (Ein Chorherrenbuch. Geschichte und Beschreibung der bestehenden und Anführung der aufgehobenen Chorherrenstifte: Augustiner und Prämonstratenser in Österreich-Ungarn, Deutschland und der Schweiz, 1883)
Keywords: 🇦🇹 austria (general); 🇨🇭switzerland (general); 🇩🇪 germany (general)

Geschichte des Prämonstratenser-Stiftes Schlägl in Oberösterreich - Pröll, Laurenz (Ein Chorherrenbuch. Geschichte und Beschreibung der bestehenden und Anführung der aufgehobenen Chorherrenstifte: Augustiner und Prämonstratenser in Österreich-Ungarn, Deutschland und der Schweiz, 1883)
Keywords: schlägl

Notice sur l'auteur de la Chronique de Saint-Marien (Robert d'Auxerre) et sur une nouvelle édition de cet ouvrage - Quantin, M. (Bulletin de la Société des Sciences Historiques et Naturelles de l'Yonne, 1883)
Keywords: 👤 robert of auxerre

Deux documents du XIIe siècle concernant l'abbaye de Floreffe - R., E. (Analectes pour servir à l'Histoire ecclésiastique de la Belgique, 1883)
Keywords: floreffe

Geschichte des Stiftes Geras - Ruhietl, Romuald (Ein Chorherrenbuch. Geschichte und Beschreibung der bestehenden und Anführung der aufgehobenen Chorherrenstifte: Augustiner und Prämonstratenser in Österreich-Ungarn, Deutschland und der Schweiz, 1883)
Keywords: geras

De voormalige abdijkerk van Tongerloo en hare kunstschatten - Spilbeeck, Waltmann van (Drukkerij van "De Vlaamsche School", 1883)
Keywords: tongerlo

De abdij Bloemhof te Wittewierum in de 13de eeuw: bijdragen tot de geschiedenis van kerk en beschaving in Nederland - Wybrands, Aemilius Willem (Verhandelingen der Koninklijke Akademie van Wetenschappen te Amsterdam, Afdeeling Letterkunde, 1883)
Keywords: bloemhof

Das Prämonstratenser-Stift Wilten in Tirol - Zacher, Adrian (Ein Chorherrenbuch. Geschichte und Beschreibung der bestehenden und Anführung der aufgehobenen Chorherrenstifte: Augustiner und Prämonstratenser in Österreich-Ungarn, Deutschland und der Schweiz, 1883)
Keywords: wilten

Beschreibung and kurze Geschichte des Pramonstratenser-Chorherrenstiftes Neu-Reisch (Nova Rise) in Mähren - Zidek, Cyrill (Ein Chorherrenbuch. Geschichte und Beschreibung der bestehenden und Anführung der aufgehobenen Chorherrenstifte: Augustiner und Prämonstratenser in Österreich-Ungarn, Deutschland und der Schweiz, 1883)
Keywords: nová říše

Aus des Klosters Mildenfurth vergangener Zeit - Aster, Georg (Bornschein & Lebe, 1882)
Keywords: mildenfurth

Urkunde vom Jahre 1570, das Kloster Barthe betreffend - Deiter, Heinrich (Jahrbuch der Gesellschaft für Bildende Kunst und Vaterländische Altertumer zu Emden, 1882)
Keywords: barthe

On the Praemonstratensian Abbey of St. Radegund, Bradsole in Polton, near Dover - Hope, W.H. St John (Archaeologia Cantiana, 1882)
Keywords: bradsole

Der hl. Gottfried, Graf von Cappenberg, Praemonstratenser-Mönch, und das Kloster Cappenberg - Husing, Augustin (Theissing, 1882)
Keywords: cappenberg

L'abbaye de Prémontré en 1882 - Madelaine, Godefroid (Imprimerie de F. Le Blanc-Hardel, 1882)
Keywords: prémontré

Memorienbuch des Klosters Wenau - Oidtman, Ernst von (Zeitschrift des Aachener Geschichtsvereins, 1882)
Keywords: wenau

Notice historique sur l'ancien refuge de l'abbaye de Saint-André-au-Bois à Hesdin - Robert, François-Joseph (Bulletin de la Société des antiquaires de la Morinie, 1882)
Keywords: hesdin

Notice historique sur l'abbaye de N.-D. de Licques, de l'ordre de Prémontré - Rozé, Jean-François (Impr. de C. Le Roy, 1882)
Keywords: licques

Die Exemtion des Klosters Steingaden von der Jurisdiktion des Augsburger Bischofs - Volkmar, Christian (Forschungen zur deutschen Geschichte, 1882)
Keywords: steingaden

Die Prämonstratenser-Abtei Rommersdorf : nach einer Handschrift und Urkunde-Sammlung des Weihbischofs W.A. Günther - Wegeler, Julius (Schuth, 1882)
Keywords: rommersdorf

Zur Geschichte des Bischofs Anselm von Havelberg - Winter, Franz (Zeitschrift für Kirchengeschichte, 1882)
Keywords: 👤 anselm of havelberg

Cartulaire de l'abbaye de Floreffe, de l'ordre de Prémontré - Barbier, Joseph; Barbier, Victor (Analectes pour servir à l'histoire ecclésiastique de la Belgique, 1881)
Keywords: floreffe

Cartulaire de l'abbaye de Bucilly - Barthélemy, Édouard de (Annales de la Société historique et archéologique de Château-Thierry, 1881)
Keywords: bucilly

Notes on the past History of the Church of Holy Trinity, Cambridge - Barton, J. (Proceedings of the Cambridge Antiquarian Society, 1881)
Keywords: cambridge

Das Necrologium der vormaligen Prämonstratenser-Abtei Arnstein a.d. Lahn - Becker, Wilhelm (Annalen des Vereins für nassanische Alterthumskunde und Geschichtsforschung, 1881)
Keywords: arnstein

Notice historique sur le sanctuaire de Sainte-Marguerite à La Rochelle (Ancienne Chapelle des Oratoriens et des Frères) - Braud, Stanislas (Imprimierie P. Dubois et L. Mehaignery, 1881)
Keywords: la rochelle

Chartes relatives à la donation des dîmes de Lonlay-le-Tesson - Contades, Gérard de (Notice sur la commune de Lonlay-le-Tesson, 1881)
Keywords: lonlay-le-tesson

Les Prémontrés à Paris - Daras, Louis (La Cour d'honneur de Marie, 1881)
Keywords: paris (college); paris (hospital)

Oeyreluy et la Porte romane de son église - Dufourcet, Eugène (Bulletin de la Société de Borda, 1881)
Keywords: oeyreluy

Die Abteikirche zu Arnstein an der Lahn. Kurzgefasste Baugeschichte und architektonische Beschreibung - Görz, Richard (C. Limbarth, 1881)
Keywords: arnstein

Über die Heimat des Chronisten Burchard von Ursperg - Hartmann, Julius (Württembergische Vierteljahrshefte für Landesgeschichte, 1881)
Keywords: 👤 burchard of ursberg

Leben des heiligen Norbert, Erzbischofs von Magdeburg : nebst der Lebensbeschreibung des Grafen Gottfried von Kappenberg und Auszügen aus verwandten Quellen - Hertel, Gustav (Geschichtschreiber der deutschen Vorzeit, 1881)
Keywords: cappenberg; 👤 norbert of xanten

Iets over eenige kloosters van de orde van Premonstreit in Friesland - Jorritsma, A. (Pius Almanak: Jaarboek van katholiek Nederland, 1881)
Keywords: 🇳🇱 netherlands (general)

Das Chorgestühl in der ehemaligen Abtei Cappenberg in Westfalen - Nagel, A. (Zeitschrift für Bauwesen, 1881)
Keywords: cappenberg

Die Wandgemälde im frühern Prämonstratenserkloster der Burg Brandenburg - Schultz, Alwin (Jahresbericht über den historischen Verein zu Brandenburg a. d. H., 1881)
Keywords: brandenburg:st marien

Die Wandgemälde im frühern Prämonstratenserkloster der Burg Brandenburg - Schultz, Alwin (Jahresbericht über den historischen Verein zu Brandenburg a. d. H., 1881)
Keywords: brandenburg:st marien

Notice historique sur le monastère de St. Nicolas de l'Ordre de Prémontré, dans la ville de St. Quentin - Sourmais, G. (La Cour d'honneur de Marie, 1881)
Keywords: saint-quentin

Inventaire de l'abbaye de l'Huveaune - Albanès (Revue des sociétés savantes de la France et de l'étranger, 1880)
Keywords: huveaune

Don de l'Hôtel-Dieu de Dammartin-en-Goële à l'abbaye de Chambrefontaine en 1263 - Becheret, A. (La Revue de Goële, 1880)
Keywords: chambrefontaine; dammartin-en-goële

Les Prémontrés en Croatie - Daras, Louis (La Cour d'honneur de Marie, 1880)
Keywords: 🇭🇷 croatia (general)

Anselm von Havelberg - Dombrowski, Eugen (Albert Rosbach'schen Buchdruckerei, 1880)
Keywords: 👤 anselm of havelberg

Quelques comtes de Brienne et l'abbaye de Beaulieu, d'après les pièces originales - Georges, Etienne (Annuaire de l'Aube, 1880)
Keywords: beaulieu

Deux pierres tumulaires de l'abbaye de l'Ile-Dieu - Le Breton, Gaston (Revue des sociétés savantes de la France et de l'étranger, 1880)
Keywords: isle-dieu

Zur Verfassungsgeschichte des Rigaschen Domcapitels - Mettig, Constantin (Mittheilungen aus dem Gebiete der Geschichte Liv-, Ehst- und Kurland's ; herausgegeben von der Gesellschaft für Geschichte und Alterthumskunde der russischen Ostsee-Provinzen, 1880)
Keywords: rīga

Das alte Bethaus Allerheiligen zu Strassburg - Müllenheim von Rechberg, Hermann von (Bulletin de la Société pour la conservation des monuments historiques d'Alsace, 1880)
Keywords: strasbourg

Saint-Just-en-Chaussée, étude historique et archéologique - Pihan, Louis (Mémoires de la Société Académique d’Archéologie, Sciences et Arts du Département de l’Oise, 1880)
Keywords: saint-just-en-chaussée

Wandmalereien im Prämonstratenser-Kloster zu Brandenburg - Schultz, Alwin (Jahrbuch der Preußischen Kunstsammlungen, 1880)
Keywords: brandenburg:st marien

Clef de voûte armoriée de la chapelle de St-Jean de la Castelle (Landes) - Sorbets, L. (Revue de Gascogne, 1880)
Keywords: la castelle

Geschichte der Bischöfe Petrus, Ludolf und Friedrich von Ratzeburg. 1236-1257 - Viereck, Ludwig (1880)
Keywords: 👤 ludolf of ratzeburg

L'Ordre de Prémontré: Etude historique et archéologique. Origines—Grandeur—Décadence—Restauration. XVII. Schinveld. Gangelt. Jabeek. (Le courrier de la Meuse, 1879)
Keywords: gangelt

L'Ordre de Prémontré: Etude historique et archéologique. Origines—Grandeur—Décadence—Restauration. XVI. Kessel et Helden (Le courrier de la Meuse, 1879)
Keywords: helden; kessel

L'Ordre de Prémontré: Etude historique et archéologique. Origines—Grandeur—Décadence—Restauration. XV. Keyserbosch, Buggenum et Neer (Le courrier de la Meuse, 1879)
Keywords: buggenum; keizerbosch

L'Ordre de Prémontré: Etude historique et archéologique. Origines—Grandeur—Décadence—Restauration. XIII. Blerick (Le courrier de la Meuse, 1879)
Keywords: blerick

L'Ordre de Prémontré: Etude historique et archéologique. Origines—Grandeur—Décadence—Restauration. XII. Oirsbeek (Le courrier de la Meuse, 1879)
Keywords: oirsbeek

L'Ordre de Prémontré: Etude historique et archéologique. Origines—Grandeur—Décadence—Restauration. X. Geleen (Le courrier de la Meuse, 1879)
Keywords: geleen

L'Ordre de Prémontré: Etude historique et archéologique. Origines—Grandeur—Décadence—Restauration. IX. Bocholtz (Le courrier de la Meuse, 1879)
Keywords: bocholtz

L'Ordre de Prémontré: Etude historique et archéologique. Origines—Grandeur—Décadence—Restauration. VIII. Simpelveld (Le courrier de la Meuse, 1879)
Keywords: simpelveld

Geschichte des Kurortes Allerheiligen im badischen Schwarzwald von Gründung des Klosters bis auf die neuste Zeit - Boeckh, Christian Friedrich von (Schauenburg, 1879)
Keywords: allerheiligen

Chronique [Abbaye de Beaulieu dans l'Aube] - Georges, Etienne (Revue de Champagne et de Brie, 1879)
Keywords: beaulieu

Beiträge zur Geschichte des Prämonstratenser-Marienstifts zu Heinsberg - Kessel, Johannes Hubertus (Zeitschrift des Aachener Geschichtsvereins, 1879)
Keywords: heinsberg

A travers la France en 1422 - Ledru, Ambroise (Revue historique et archéologique du Maine, 1879)
Keywords: perray-neuf

Seal of Wendling Abbey - Manning, C. R. (Norfolk Archaeology, 1879)
Keywords: wendling

L'abbaye de Licques - Poucques d'Herbinghem, A. de (Bulletin de la Société des Antiquaires de Picardie, 1879)
Keywords: licques

Talley Abbey - Price, David Long (Archaeologia Cambrensis, 1879)
Keywords: talley

Het hoogadelijk, vrij wereldlijk stift te Bedburg bij Kleef - Sloet, L. A. J. W. Baron (Verhandelingen der Koninklijke Akademie van Wetenschappen, 1879)
Keywords: bedburg

On the recent excavations on the site of Dale Abbey, Derbyshire - St John Hope, W.H. (Derbyshire Archaeological Journal, 1879)
Keywords: dale

Das Prämonstratenserkloster Bedburg bei Kleve - Terwelp, Gerhard (Niederrheinischer Geschichtsfreund, 1879)
Keywords: bedburg

Gesta abbatum Orti Sancte Marie: Gedenkschriften van de abdij Mariëngaarde in Friesland. Naar het te Brussel bewaarde handschrift - Wybrands, Aemilius Willem (H. Kuipers, 1879)
Keywords: mariëngaarde

Zur Geschichte der Abtei Arnstein - Zaun, Johann (Annalen des Vereins für Nassauische Altertumskunde und Geschichtsforschung, 1879)
Keywords: arnstein

Report on the Excavations at Dale Abbey - Cox, J.C. (The Derby Mercury, 1878)
Keywords: dale

Trümmer des Prämonstratenser-Klosters Gottesgnaden (Geschichtsblätter für Stadt und Land Magdeburg : Mitteilungen des Vereins für Geschichte und Altertumskunde des Herzogtums und Erzstifts Magdeburg, 1878)
Keywords: gottesgnaden

Historical memorials of Beauchief Abbey - Addy, Sidney Oldall (J. Parker, 1878)
Keywords: beauchief

Les découvertes de l'Abbaye d'Ardenne - Beaurepaire, E. de (Bulletin de la Société des antiquaires de Normandie, 1878)
Keywords: ardenne

The Royal Charters Relating to the Town and County of Carmarthen and the Abbeys of Talley and Tygwyn-ar-Daf - Daniel-Tyssen, J.R. (Spurrell, 1878)
Keywords: talley

Cartulaire de la Luzerne - Dubosc, François (Imprimerie Jacqueline Fils, 1878)
Keywords: la lucerne

A Sketch of the Premonstratensian Order and its houses in Great Britain and Ireland - Geudens, F.M. (Burns and Oates, 1878)
Keywords: 🇬🇧 great britain (general); 🇮🇪 ireland (general)

Notice sur le prieuré de Crécy - Guelliot, O. (Revue de Champagne et de Brie, 1878)
Keywords: crécy

The Annals of Lough Key - Healy, John (The Irish Monthly, 1878)
Keywords: lough key

Urkundenbuch des Klosters Unser Lieben Frauen zu Magdeburg - Hertel, Gustav (Geschichtsquellen der Provinz Sachsen und des Friestaates Anhalt, 1878)
Keywords: magdeburg

Journal historique écrit dans l'Abbaye de Saint-Jean - Janvier, A. (La Picardie: revue historique, archéologique & littéraire, 1878)
Keywords: amiens

Cartulaire de l'abbaye de la Chapelle-aux-Planches. Chartes de Montierender, de Saint-Etienne et de Toussaints de Chalons, d'Andecy, de Beaulieu et de Rethel - Lalore, Charles (Collection des principaux cartulaires du diocèse de Troyes, 1878)
Keywords: chapelle aux planches

Quelques sceaux du diocèse de Gand: Abbaye de S. Marie de Tronchiennes - Lavant, J.B. (Messager des Sciences historiques de Belgique, 1878)
Keywords: drongen

Monastère et abbaye royale de Saint-Jean-De-La-Castelle à Dufort ou Duhort - Légé, Joseph (Impr. de Ragot, 1878)
Keywords: la castelle

Das Frauenkloster Schillingskapellen - Merlo, J.H. (Annalen des Historischen Vereins für den Niederrhein, 1878)
Keywords: schillingskapellen

Une colonie agricole au XIIe siècle (Abbaye de Corneux) - Morey (Académie des Sciences, Belles-Lettres et Arts de Besançon, 1878)
Keywords: corneux

Der fränkische Lehnhof und die Pfarrei Immekeppel - Müller, Aegidius (Annalen des Historischen Vereins für den Niederrhein, 1878)
Keywords: immekeppel

Un chapiteau du XIIe s. - Papillon, Léandre (La Thiérache: Bulletin de la Société archéologique de Vervins, 1878)
Keywords: thenailles

Histoire de l'abbaye de Thenailles: ordre de Prémontré - Piette, Amédée (Impr. de A. Michaux, 1878)
Keywords: thenailles

Über die Stiftungsurkunde des Prämonstratenserklosters Broda - Platner, Carl (Forschungen zur deutschen Geschichte, 1878)
Keywords: broda

Inscription murale de l'église de Durance - Sorbets, L. (Revue de Gascogne, 1878)
Keywords: durance

The alien priory of Ravendale - Venables, Edmund (Associated Architectural Societies' Reports and Papers, 1878)
Keywords: west ravendale

John de Veteripont, or Vipount (The Kendal Mercury, 1877)
Keywords: appleby; shap

Das adelige Frauenkloster Meer bei Neuss - Keussen, Hermann (Die Heimath: Wochenblatt für Kunde der niederrhenischen Geschichte, mit Einschluss der Sagen, Legenden, Gebräuche, etc., 1877)
Keywords: meer

Das adelige Frauenkloster Meer bei Neuss - Keussen, Hermann (Die Heimath: Wochenblatt für Kunde der niederrhenischen Geschichte, mit Einschluss der Sagen, Legenden, Gebräuche, etc., 1877)
Keywords: meer

Das adelige Frauenkloster Meer bei Neuss - Keussen, Hermann (Die Heimath: Wochenblatt für Kunde der niederrhenischen Geschichte, mit Einschluss der Sagen, Legenden, Gebräuche, etc., 1877)
Keywords: meer

Das adelige Frauenkloster Meer bei Neuss - Keussen, Hermann (Die Heimath: Wochenblatt für Kunde der niederrhenischen Geschichte, mit Einschluss der Sagen, Legenden, Gebräuche, etc., 1877)
Keywords: meer

Das adelige Frauenkloster Meer bei Neuss - Keussen, Hermann (Die Heimath: Wochenblatt für Kunde der niederrhenischen Geschichte, mit Einschluss der Sagen, Legenden, Gebräuche, etc., 1877)
Keywords: meer

Das adelige Frauenkloster Meer bei Neuss - Keussen, Hermann (Die Heimath: Wochenblatt für Kunde der niederrhenischen Geschichte, mit Einschluss der Sagen, Legenden, Gebräuche, etc., 1877)
Keywords: meer

Das adelige Frauenkloster Meer bei Neuss - Keussen, Hermann (Die Heimath: Wochenblatt für Kunde der niederrhenischen Geschichte, mit Einschluss der Sagen, Legenden, Gebräuche, etc., 1877)
Keywords: meer

Urkunden über das Zehntrecht der Abtei Meer im Gebiete von Grefeld - Keussen, Hermann (Die Heimath: Wochenblatt für Kunde der niederrhenischen Geschichte, mit Einschluss der Sagen, Legenden, Gebräuche, etc., 1877)
Keywords: meer

Incendie du monastère de Divielle, d'après un document inédit - Abbadie, François (Bulletin de la Société de Borda, 1877)
Keywords: divielle

Relation de Hayton, prince d'Arménie - Backer, Louis de (L'Extrême Orient au Moyen-Âge d'après les manuscrits d'un flamand de Belgique moine de Saint-Bertin à Saint-Omer et d'un prince d'Arménie moine de Prémontré à Poitiers, 1877)
Keywords: 👤 hayton of corycus

Documents concernant Gouy-lez-Piéton et Arquennes, extraits du cartulaire de Floreffe - Barbier, J. (Analectes pour servir à l'histoire ecclésiastique de la Belgique, 1877)
Keywords: floreffe

Acta sancti Petri in Augia : vier Quellenschriften des 13. Jahrhunderts aus dem Kloster Weissenau bei Ravensburg - Baumann, Franz Ludwig (G. Braun, 1877)
Keywords: weissenau

Premonstráti v Čechách a na Moravě: Stručné vypsáni osudu jednotlivých bud ještě stávajících neb již vyhlazených Klášteru toho řadu dle roku jich založení ; co dárck k páté padesátileté památce přenešeni sv. Norberta - Čermák, D̆ominic (Nákl. kanonie Strahovské, 1877)
Keywords: 🇨🇿 czechia (general)

Svatý Norbert, arcibiskup Magdeburský, patriarcha a zakladatel řádu ... - Čermak, Dominik Karel (Cyrillo-Methodějská kněhtiskárna, Nakl. kanonie Strahovské, 1877)
Book digitized by Google from the library of the University of Michigan and uploaded to the Internet Archive by user tpb.
Keywords: 👤 norbert of xanten

Notre Dame de Thurocz - Daras (La Cour d'honneur de Marie, 1877)
Keywords: klaštor pod znievom

Excursion a l'abbaye de Mondaye - Des Diguères, Victor (Annuaire des cinq départements de l'ancienne Normandie, 1877)
Keywords: mondaye

Beredeneerde inventaris van de oorkonden en bescheiden van het adelijk klooster St. Gerlach, berustende op het Provinciaal Archief van Limburg - Franquinet, Guillaume Désiré (Ter Provinciale Griffie, 1877)
Keywords: sint-gerlach

Güterverzeichnis des Klosters Langen in Ostfriesland - Friedländer, E. (Jahrbuch der Gesellschaft für bildende Kunst und vaterländische Altertümer zu Emden, 1877)
Keywords: langen

Kloster Adelberg - Klemm, Alfred (Staatsanzeiger für Württemberg. Besondere Beilage, 1877)
Keywords: adelberg

Die Handschriften und ältesten Drucke der Klosterbibliothek Unser Lieben Frauen - Knaut, Karl (Jahrbuch des Pädagogiums zum Kloster Unser Lieben Frauen in Magdeburg, 1877)
Keywords: magdeburg

La Statue funéraire du Perray-Neuf - Ledru, Ambroise (Revue historique et archéologique du Maine, 1877)
Keywords: perray-neuf

Die Kirche zu Lübsee bei Rehna - Lisch, Georg Christian Friedrich (Jahrbücher des Vereins für Mecklenburgische Geschichte und Altertumskunde, 1877)
Keywords: lübsee

Über den Capitelsaal des Klosters Rehna - Lisch, Georg Christian Friedrich (Jahrbücher des Vereins für Mecklenburgische Geschichte und Altertumskunde, 1877)
Keywords: rehna

Das ehemalige Prämonstratenser-Kloster Neustift bis zur Säkularisation 1140-1802 - Prechtl, Johann Baptist (Beiträge zur Geschichte der Stadt Freising, 1877)
Keywords: neustift

Geschichte des Prämonstratenserstiftes Schlägl im oberen Mühlviertel - Pröll, Laurenz (F.J. Ebenhöch, 1877)
Keywords: schlägl

Medieval Wall Painting at Upchurch - Robertson, Scott (Archaeologia Cantiana, 1877)
Keywords: upchurch

Emo von Wittewierum - Van Slee, Jacobus Cornelis (Allgemeine Deutsche Biographie, 1877)
Keywords: bloemhof

Das Kloster Schillingskapellen im Pfarrbezirk Heimerzheim (Schluss) - Berrisch, Engelbert (Die Heimath: Wochenblatt für Kunde der niederrheinischen Geschichte, mit Einschluss der Sagen, Legenden, Gebräuche, etc, 1876)
Keywords: schillingskapellen

Das Kloster Schillingskapellen im Pfarrbezirk Heimerzheim - Berrisch, Engelbert (Die Heimath: Wochenblatt für Kunde der niederrheinischen Geschichte, mit Einschluss der Sagen, Legenden, Gebräuche, etc, 1876)
Keywords: schillingskapellen

Nécrologe de l'abbaye de Floreffe, de l'ordre de Prémontré, au diocèse de Namur - Barbier, Joseph (Impr. de Ch. Peeters, 1876)
Keywords: floreffe

Norbert von Prémontré und Magdeburg - Bernheim, Ernst (Historische Zeitschrift, 1876)
Keywords: 👤 norbert of xanten

Mots bretons dans les chartes de l’abbaye de Beauport (Côtes du Nord) - d'Arbois de Jubainville, H. (Revue Celtique, 1876)
Keywords: beauport

Geschichte des Bisthums Ratzeburg. 2: Der Bischof Evermod - Kuhle, J. (1876)
Keywords: 👤 evermod of ratzeburg

Kościoły i rzeźby Duninowskiego w Strzelnie na Kujawach oraz ruina kościoła P. Maryi w Inowrocławiu : przyczynek do dziejów sztuki 12 wieku - Łuszczkiewicz, Władysław (Druk. "Czasu", 1876)
Keywords: strzelno

St. Luzi bei Chur vom zweiten Jahrhundert bis zur Gegenwart: Geschichte der Kirche, des Klosters und des Seminars - Mayer, Johann Georg (M. Rieger'sche Buchhandlung, 1876)
Keywords: chur (st luzi)

Cartulaire de l'abbaye de Morienval et chartes de l'abbaye de Lieu-Restauré - Peigné-Delacourt, Achille (Comité archéologique de Senlis, 1876)
Keywords: lieu-restauré

Histoire de Prémontré, précédé de la Vie de Saint Norbert - Valissant, Armand (Impr. H. Jacob, 1876)
Keywords: prémontré; 👤 norbert of xanten

Het Wittevrouwen-klooster te Utrecht, annis 1556 en 1576 - Van Lommel, A. (Archief voor de geschiedenis van het aartsbisdom Utrecht, 1876)
Keywords: wittevrouwen

Splendeur et ruines de l'abbaye de Joyenval - Maquet, A. (L'Industriel de Saint-Germain-en Laye, 1875)
Keywords: joyenval

Nécrologe et Tombeaux de l'abbaye de Joyenval - Maquet, A. (L'Industriel de Saint-Germain-en Laye, 1875)
Keywords: joyenval

Nécrologe et Tombeaux de l'abbaye de Joyenval - Maquet, A. (L'Industriel de Saint-Germain-en Laye, 1875)
Keywords: joyenval

L'abbaye de Joyenval - Maquet, A. (L'Industriel de Saint-Germain-en Laye, 1875)
Keywords: joyenval

L'abbaye de Joyenval - Maquet, A. (L'Industriel de Saint-Germain-en Laye, 1875)
Keywords: joyenval

L'abbaye de Crécy, ordre de Prémontré, au diocèse de Reims, son origine et sa ruine (1140-130) - Noel, D. (Echo de Givet, 1875)
Keywords: crécy

À Chaumont-Porcien (Ardennes), une trouvaille assez rare (Bulletin du Diocèse de Reims, 1875)
Keywords: chaumont-porcien

Documents concernant le prieuré de Wanze, extraits du cartulaire de l'abbaye de Floreffe - Barbier, Joseph (Analectes pour servir à l'histoire ecclésiastique de la Belgique, 1875)
Keywords: wanze

Chronik der Vorderstadt Neubrandenburg: Nebst zwei Anhängen: Über die sogenannten Prilwitzer Idole im Großherzoglichen Altertums-Kabinett zu Neustrelitz, und: Geschichte des Prämonstratenser-Klosters zu Broda. - Boll, Franz (Mitteldeutsche Stadtgeschichte in Wort und Bild, 1875)
Keywords: broda

Histoire des abbayes de Dommartin et de Saint-André-au-Bois, ordre de Prémontré, au diocèse d'Amiens - Calonne, Albéric de (Sueur-Charrey, 1875)
Keywords: dommartin; saint-andré-au-bois

Cartulaire de l'Abbaye de Basse-Fontaine. Chartes de Beauvoir - Lalore, Charles (Collection des principaux cartulaires du diocèse de Troyes, 1875)
Keywords: basse fontaine

Note sur le cartulaire de St. Yved de Braine - Leclercq de la Prairie, J. (Bulletin de la Société archéologique, historique et scientifique de Soissons, 1875)
Keywords: braine

Histoire de l'abbaye de Notre-Dame-de Vermand - Lecocq, Georges (Imprimerie Ch. Poette, 1875)
Keywords: vermand

Cartulaire de Tinselve - Pécheur, L'Abbé (Bulletin de la Société archéologique de Soissons, 1875)
Keywords: tinselve

Essai sur la vie claustrale et l'administration intérieure dans l'ordre de Prémontré au XIe et au XIIe siècle - Richou, Gabriel (Positions des thèses, 1875)
Keywords: 📚 premonstratensian (general)

Essai sur la vie claustrale et l’administration intérieure dans l’ordre et l’abbaye de Prémontré au XIIe et au XIIIe siècle - Richou, Gabriel (École nationale des chartes, 1875)
Keywords: 📚 premonstratensian (general)

Streitigkeiten zwischen der Stadt Arnsberg und dem Kloster Wedinghausen - Tücking, Karl (Blätter zur näheren Kunde Westfalens : Organ des Historischen Vereins für das Herzogthum Westfalen, 1875)
Keywords: wedinghausen

Het klooster Bethlehem te ' s-Gravenhage - Van der Horst, J.D. (Bijdragen voor de geschiedenis van het Bisdom van Haarlem, 1875)
Keywords: den haag

Énumération des gravures consacrées au monastère de Prémontré - Fleury, Édouard (Bulletin de la Société académique de Laon, 1874)
Keywords: prémontré

Das Kloster Himmelspforte bei Wyhlen - Gmelin, Moritz (Zeitschrift für die Geschichte des Oberrheins, 1874)
Keywords: himmelspforte (germany)

Roche Abbey, Yorkshire; and Beauchief Abbey, Derbyshire - Hills, Gordon M. (Journal of the British Archaeological Association, 1874)
Keywords: beauchief

Notice sur l'église de l'ancienne abbaye des Prémontrés à Ninove - Limburg-Stirum, Thierry de (Messager des sciences historiques ou Archives des arts et de la bibliographie de Belgique, 1874)
Keywords: ninove

Notice sur deux chapiteaux trouvés dans la forêt de Saint-Gobain - Loy, N. (Bulletin de la Société Académique de Laon, 1874)
Keywords: prémontré

Essai historique sur l'abbaye de Mondaye de l'Ordre de Prémontré - Madeleine, Godefroid (F. LeBlanc-Hardel, 1874)
Keywords: mondaye

Die Prämonstratenser-Abtei Knechtsteden - Raschdorff, J. C. (Zeitschrift für Bauwesen, 1874)
Keywords: knechtsteden

Dziedziniec w klasztorze Panien Norbertanek, na Zwierzyńcu, w Krakowie - R. (1873)
Keywords: zwierzyniec

Monasterio ó Abadía de Aguilar de Campoo - Assas, Manuel de (Museo español de antigüedades, 1873)
Keywords: aguilar de campoo

Sepulcros de Aguilar de Campoo - Assas, Manuel de (Museo español de antigüedades, 1873)
Keywords: aguilar de campoo

Documents relatifs à Corroy-le-Château, extraits du Cartulaire de l'abbaye de Floreffe - Barbier, Joseph (Analectes pour servir à l'Histoire ecclésiastique de la Belgique, 1873)
Keywords: floreffe

Documents relatifs a Senenne, sous Anhée (Namur), extraits du cartulaire de l'abbaye de Floreffe - Barbier, Joseph (Analectes pour servir à l'Histoire ecclésiastique de la Belgique, 1873)
Keywords: floreffe

Note on the Seal of Beauchief Abbey - Boulter, W.C. (Proceedings of the Society of Antiquaries of London, 1873)
Keywords: beauchief

Michael Neander's Bericht vom Kloster Ilfeld : ein Beitrag zur Geschichte des 16. Jahrhunderts ; zum ersten Male herausgegeben - Bouterwek, Rudolf (Jahresbericht über das Königliche Pädagogium zu Ilfeld, 1873)
Keywords: ilfeld

Dziedziniec w klasztorze Panien Norbertanek, na Zwierzyńcu w Krakowie - Matejko, Jan (Album Jana Matejki, 1873)
Keywords: zwierzyniec

Manslag in het Klooster Mariëngaarde, in 1543 - Nanninga Uitterdijk, Jurjen (De Vrije Fries, 1873)
Keywords: mariëngaarde

Le Bienheureux Henry de Reims et la Bienheureuse Ermengarde de Roucy, de l'Ordre de Prémontré - Noel, Albert (Bulletin du Diocèse de Reims : Revue religieuse historique et littéraire, 1873)
Keywords: gérigny; valsery

Découverte de deux chartes latines du XIIIe siècle - Papillon, Léandre (Bulletin de la Société archéologique de Vervins, 1873)
Keywords: prémontré

L'abbaye de St-Michel d'Anvers ver la fin du XVIe s. - Ridder, C.-B. (Analectes pour servir à l'histoire ecclésiastique de la Belgique, 1873)
Keywords: antwerp

Das Kloster Wedinghausen und das Gymnasium zu Arnsber - Tücking, Karl (Blätter zur näheren Kunde Westfalens, 1873)
Keywords: wedinghausen

Sur l'origine et l'histoire de Bury, église et prieuré compris - Warmé, Antoine-Joseph (Mouy et ses environs : Angy, Bury, Ansacq, Cambronne, Heilles, Hondainville, Neuilly, Mello, Mouchy-le-Chatel, Saint-Félix, Thury-sous-Clermont, Ully-Saint-Georges, 1873)
Keywords: bury

Tor Abbey (The Exeter Flying Post or, Trewman's Plymouth and Cornish Advertiser, 1872)
Keywords: torre

Charters of Cumbwell Priory (Archaeologia Cantiana, 1872)
Keywords: combwell

Documents concernant la paroisse de Thiméon, extraits du cartulaire de l'abbaye de Floreffe - Barbier, Joseph (Analectes pour servir à l'Histoire ecclésiastique de la Belgique, 1872)
Keywords: floreffe

Réforme du monastère de Wenau vers la fin du XVe siècle - Barbier, Joseph (Analectes pour servir à l'histoire ecclésiastique de la Belgique, 1872)
Keywords: wenau

Documents extraits du cartulaire de Grimbergen - De Ridder (Analectes pour servir à l'histoire ecclésiastique de la Belgique, 1872)
Keywords: grimbergen

The ancient Church of St. Nicholas, Carrickfergus, diocese of Connor. A report to the Right Rev. Robert Knox, Lord Bishop of Down and Connor and Dromore - Drew, Thomas (Ponsonby and Mayne, 1872)
Keywords: carrickfergus

Die ältere Geschichte des Klosters Steinfeld - Ennen, Leonard (Annalen des Historischen Vereins für den Niederrhein, 1872)
Keywords: steinfeld

Die Chronik Emos and Menkos von Floridus Hortus - Gelhorn, Johannes (Universität Göttingen, 1872)
Keywords: bloemhof

Postel, son abbaye et son église - Gife, E.-L. (Annales de l'Académie royale d'archéologie de Belgique, 1872)
Keywords: postel

Hales Owen Abbey (With Illustrations) - Holliday, J.R. (Transactions and Proceedings. Birmingham and Midland Institute Archaeological Section, 1872)
Keywords: halesowen

L'abbaye de Saint-André-au-Bois: Chroniques de cette maison - Laplane, Henri de (Bulletin de la Société des antiquaires de la Morinie, 1872)
Keywords: saint-andré-au-bois

Vrejlev Kloster og Klosterkirke - Løffler, J.B. (Ny kirkehistoriske Samlinger, 1872)
Keywords: vrejlev

Das Leben des heiligen Dieners Gottes Aldericus aus dem Praemonstratenser-Orden, dessen wunderthätige Gebeine in der frühern Klosterkirche, jetzigen Pfarrkirche zu Füssenich aufbewahrte werden: nebst einem Andachtsbuch zur Ehre des h. Aldericus - Schmitz, N. (Rabuske, 1872)
Keywords: füssenich

Prémontré : Etude sur l'abbaye de ce nom, sur l'ordre qui y a pris naissance, ses progrès, ses épreuves et sa décadence - Taiée, Charles (1872)
Keywords: prémontré

Hagiographie norbertine: 5 mars, Bienheureuse Garemberte (La Cour d'honneur de Marie, 1871)
Keywords: macquincourt

Documents concernant Grand-Leez et Sauvenière, extraits du cartulaire de l'abbaye de Floreffe - Barbier, Joseph (Analectes pour servir à l'Histoire ecclésiastique de la Belgique, 1871)
Keywords: floreffe

Documents concernant Sautour et Aublain, extraits du cartulaire de l'abbaye de Floreffe - Barbier, Joseph (Analectes pour servir à l'Histoire ecclésiastique de la Belgique, 1871)
Keywords: floreffe

Die ältere Geschichte des Klosters Steinfeld - Ennen, Leonard (Annalen des Historischen Vereins für den Niederrhein, 1871)
Keywords: steinfeld

Bau-Reliquien des ehemaligen Prämonstratenser-Klosters Gottesgnade bei Calbe - G.A. von M. (Geschichtsblätter für Stadt und Land Magdeburg : Mitteilungen des Vereins für Geschichte und Altertumskunde des Herzogtums und Erzstifts Magdeburg, 1871)
Keywords: gottesgnaden

The annals of Loch Cé : a chronicle of Irish affairs from A.D. 1014 to A.D. 1590 - Hennessy, W.M. (1871)
Keywords: lough key

Decorative Pavement Tiles on the site of Hales Owen Abbey - Holliday, J.R. (Archaeological Journal, 1871)
Keywords: halesowen

Date de la fondation du prieuré de Chapelle-lez-Herlaimont - Lemaigre, C. (Documents et Rapports de la Société Paléontologique et Archéologique de l'Arrondissement Judiciaire de Charleroi, 1871)
Keywords: herlaimont

De abdij van Bern. Bijdragen tot de kerkelijke geschiedenis van Nederland. - van Lommel, Antonius (De Dietsche Warande, 1871)
Keywords: berne

Documents concernant Trazegnies, extraits du cartulaire de l'abbaye de Floreffe - Barbier, Joseph (Analectes pour servir à l'Histoire ecclésiastique de la Belgique, 1870)
Keywords: floreffe

Das Nekrologium von Wilten von 1142-1698 - Brunner, Sebastian (Archiv für österreichische Geschichte, 1870)
Keywords: wilten

Notre Dame de Thurocz - Daras (La Cour d'honneur de Marie, 1870)
Keywords: klaštor pod znievom

Die Paternität über das Vinzenzstift zu Breslau - Grotefend, H. (Zeitschrift des Vereins für Geschichte Schlesiens, 1870)
Keywords: wrocław

Nekrolog der Prämonstratenster zu St. Vincenz bei Breslau - Hein, Paul; Grünhagen, Colmar (Zeitschrift des Vereins für Geschichte (und Alterthum) Schlesiens, 1870)
Keywords: wrocław

Hroznata und die Prämonstratenser-Abtei Tepl: Nach Urkunden des Stiftsarchiv - Karlik, Hugo (Druck von Carl Maasch Selbstverlag, 1870)
Keywords: teplá; 👤 hroznata of bohemia

Notice sur le prieuré de Ste-Radegonde de l'Écotière - Landau (Bulletin de la Société Archéologique du Vendômois, 1870)
Keywords: busloup

Etude sur l'abbaye de Belle-Étoile - Madelaine, Godefroid (Semaine religieuse du diocèse de Bayeux, 1870)
Keywords: belle-étoile

Breve chronicon Abbatiae Bucliiensis: Chronique abrégée de l'abbaye de Bucilly rédigée - Oudin, Casimir (H. de Coquet et G. Stenger, 1870)
Keywords: bucilly

The abbey of St Agatha, for white or Augustine canons, called Praemonstratensians, at Easby - Rowe, G. (Associated Architectural Societies Reports and Papers, 1870)
Keywords: easby

Die Kirche der Prämonstratenser-Abtei zu Kappenberg - Savels, C. August (Zeitschrift für Bauwesen, 1870)
Keywords: cappenberg

Die eingegangenen Dörfer der Abtei Bruck an der Taja und der Umgebung - Beck, J. (Notizen-Blatt der Historisch-Statistischen Section der Kais.-Königl. Mährisch-Schlesischen Gesellschaft zur Beförderung des Ackerbaues, der Natur- und Landeskunde, 1869)
Keywords: louka

Document inédits touchant le couvent des norbertines de Reckheim - Daris, J. (Bulletin de la Société Scientifique et Littéraire du Limbourg, 1869)
Keywords: rekem

Notre-Dame de Bonne-Espérance - Declèves, Charles Louis (V. Devaux, 1869)
Keywords: bonne-espérance

Houthem-Sint-Gerlach en het adelijk vrouwenstift aldaar: eene bijdrage tot de geschiedenis van het voormalig land van Valkenberg - Habets, Jos (Hollman, 1869)
Keywords: sint-gerlach

Necrologium der adelijke proosdij Sint- Gerlach - Habets, Jos (Publications de la Société historique et archéologique dans le duché de Limbourg, 1869)
Keywords: sint-gerlach

Drei Urkunden zur Geschichte des Georgs-Klosters und des Zevener Hofes zu Stade - Krause, Karl Ernst Hermann (Archiv des Vereins für Geschichte und Altertümer der Herzogtümer Bremen und Verden und des Landes Hadeln zu Stade, 1869)
Keywords: stade

Krátký dějepis bývalého kláštera premonštráků, nynější farnosti a chrámu Páně v Zábrdovicích - Pospěch, Josef (Josef Pospěch, 1869)
Keywords: zábrdovice

Árpás és a móriczhidai Szent Jakabról címzett prépostság története - Rómer, Flóris (Aigner - Rautmann, 1869)
Keywords: mórichida

Histoire de l'ancienne abbaye de Bellelay de l'Ordre des Prémontrés - Saucy, Paul-Simon (Impr. de J. Gürtler, 1869)
Keywords: bellelay

East Halton (Stamford Mercury, 1868)
Keywords: east halton

Note sur l'ancienne église de Beaurepart (Bulletin de l'Institut Archéologique Liégeois, 1868)
Keywords: beaurepart

Das Nonnenkloster Lauffen am Neckar - Bach, Max (Zeitschrift des Historischen Vereins für das Württembergische Franken, 1868)
Keywords: lauffen

Excursion à l'abbaye de Belle-Étoile - Bouet, G. (Bulletin Monumental, 1868)
Keywords: belle-étoile

Notice historique sur l’abbaye de Beaurepart à Liège - Daris, Joseph (Bulletin de l'Institut archéologique liégeois, 1868)
Keywords: beaurepart

Geschichte des Klosters Speinshart - Eder, Anton (Verhandlungen des Historischen Vereins für Oberpfalz und Regensburg, 1868)
Keywords: speinshart

Blanchland - Featherstonehaugh, Walker (Transactions of the Architectural and Archaeological Society of Durham and Northumberland, 1868)
Keywords: blanchland

Dale Abbey, Derbyshire - Fox, Samuel (The Reliquary, 1868)
Keywords: dale

Notice sur l'abbaye de St-Martin de Laon - Gomart, Charles (Bulletin de la Société académique de Laon, 1868)
Keywords: laon

Mittelalterliche Siegel aus dem Magdeburger Lande (Luchardis Edle v. Barby, vermählte v. Alsleben, Stadt Egeln, Werner Feuerhake, Deutsch-Ordens-Commende Berge, Kl. Gottesgnaden) - Mülverstedt, Georg Adalbert von (Geschichtsblätter für Stadt und Land Magdeburg, 1868)
Keywords: gottesgnaden

Le monastère du Val-des-Lys, Leliëndal - Neefs, Emmanuel (Peeters, 1868)
Keywords: leliëndaal

L'abbaye de Salival - Pierson, G. (Mémoires de la Société d'archéologie Lorraine, 1868)
Keywords: salival

Deux documents concernant les droits respectifs du chapitre de N.-D. et des religieux de l'abbaye de St-Michel à Anvers au XIIe et au XIIIe s. - Ridder, C.-B. (Analectes pour servir à l'histoire ecclésiastique de la Belgique, 1868)
Keywords: antwerp

Une relique bibliographique de l'abbaye de Salival conservée à la bibliothèque impériale - Schmit, Joseph-Alexandre (Journal de la Société d’archéologie et du Comité du Musée lorrain, 1868)
Keywords: salival

A Paper on Torre Abbey - Ashworth, Edward (Transactions of the Exeter Diocesan Architectural Society, 1867)
Keywords: torre

Notes sur le prieuré de Renissart - Devillers, Léopold (Bulletin du Cercle archéologique de Mons, 1867)
Keywords: renissart

Zur Geschichte der Abtei Steinfeld - Eich, A. (Annalen des Historischen Vereins für den Niederrhein, 1867)
Keywords: steinfeld

Die Krypta der Klosterkirche St. Wiperti in Quedlinburg - Hase, Conrad Wilhelm (Die mittelalterlichen Baudenkmäler Niedersachsens, 1867)
Keywords: quedlinburg

Beauchief Abbey - Kirke, H. (The Reliquary and Illustrated Archæologist: A Quarterly Journal and Review, 1867)
Keywords: beauchief

Essai sur le nom et l'origine de Prémontré - Marville, Martin (Comité archéologique de Noyon. Comptes rendus et mémoires, 1867)
Keywords: prémontré

Le monastère de l'Ile-Duc à Gempe, Louvain - Neefs, Emmanuel (Peeters, 1867)
Keywords: gempe

Klasztor Norbertanek w Krakowie - Anczyc, Władysław Ludwik (Tygodnik ilustrowany, 1866)
Keywords: zwierzyniec

Charters of Cumbwell Priory. Part II (Archaeologia Cantiana, 1866)
Keywords: combwell

Geschichte des Geist- und Freiadlichen Klosters Wenau sowie geschichtliche Nachrichten über die Kirspelkirchen Langerwehe und Geuenich und der Filialkirche Contzendorf - Bonn, Mathias Michael (Selbstverl. des Verf., 1866)
Keywords: wenau

Kronijken van Emo en Menko, Abten van het klooster te Wittewierum, met het vervolg van een ongenoemde - Emo; Menko (Werken. Historisch Genootschap, 1866)
Keywords: bloemhof

Das adelige Frauenkloster Meer bei Neuss - Keussen, Hermann (Klein, 1866)
Keywords: meer

Vie de Saint Norbert: fondateur de l'ordre des chanoines réguliers de Prémontré - Liguori, Alphonse de (H. Goemaere, 1866)
Keywords: 👤 norbert of xanten

Urkundenbuch des Klosters Germerode - Schmincke, Julius Ludwig Christian (Zeitschrift des Vereins für hessische Geschichte und Landeskunde. Supplement, 1866)
Keywords: germerode

Registratur over Börglum Klosters Breve (De aeldste danske archivregistraturer, 1865)
Keywords: børglum

Markerhoofd - Bakhuizen van den Brink, Reinier Cornelis (De Vrije Fries, 1865)
Keywords: monnickendam

Mémoire historique sur l'abbaye de Belchamp de l'ordre de Prémontré, au comté de Montbéliard - Bouchey, Eugène-Augustin (Imprimerie de Clerc, 1865)
Keywords: belchamp

Essai historique sur l’Abbaye de Fontaine-André (Neuchâtel) depuis sa fondation jusqu’à sa suppression avec pièces justificatives - Jeunet, François (Etrennes neuchâteloises, 1865)
Keywords: fontaine-andré

Recueil de sépultures anciennes et épitaphes de Saint-Paul de Verdun, fait en 1552, par ordonnance de M. Psaulme, évêque de Verdun, publié en 1779 avec un avis à la noblesse par l'abbé Lionnois - Lionnois, Jean-Jacques (Imprimerie Cayon-Liébault, 1865)
Keywords: verdun

L'excursion archéologique de 1864 - Pécheur (Bulletin de la Société archéologique, historique et scientifique de Soissons, 1865)
Keywords: prémontré

Abbaye de Marcheroux de l'ordre des Prémontrés et de la filiation de Saint-Josse-aux-Bois ou Dommartin - Sabatier, A. (Mémoires de la Société académique d'archéologie, sciences et arts du département de l'Oise, 1865)
Keywords: marcheroux

Die Prämonstratenser des zwölften Jahrhunderts und ihre Bedeutung für das nordöstliche Deutschland ein Beitrag zur Geschichte der Christianisierung und Germanisierung des Wendenlandes - Winter, Franz (C. Schweigger'sche Hofbuchhandlung, 1865)
Keywords: 🇩🇪 germany (general)

Geschichte der Überbringung der großen Kreuzpartikel in dem ehemaligen Kloster, jetzt Pfarrkirche zu Ellen; nebst geschichtlichen Nachrichten über das Kloster selbst - Bonn, Mathias Michael (1864)
Keywords: ellen

Abbaye de Beauport (Ordre des Prémontrés) - Geslin de Bourgogne, Jules-Henri; Barthélemy, Anatole de (Ancien Évêchés de Bretagne: Histoire et Monuments, 1864)
Keywords: beauport

Nachträge ... zu den Pröbsten von St. Georg in Stade und von Himmelpforten und den Äbtissinnen von Lilienthal - Krause, Karl Ernst Hermann (Archiv des Vereins für Geschichte und Altertümer der Herzogtümer Bremen und Verden, 1864)
Keywords: stade

L'ancienne abbaye de Saint-Feuillen - Lejeune, Thomas (Annales du Cercle archéologique de Mons, 1864)
Keywords: rœulx

Notice historique sur l'abbaye de l'Ile-Dieu - Stabenrath, Charles de (Procès verbaux de la Commission départementale des antiquités de la Seine inférieure, 1864)
Keywords: isle-dieu

Charters of Cumbwell Priory, Part 1. With a Pedigree of the Gatton Family (Archaeologia Cantiana, 1863)
Keywords: combwell

Zur Geschichte der Abtei Steinfeld - Braun, J. (Annalen des Historischen Vereins für den Niederrhein, 1863)
Keywords: steinfeld

Notre Dame de Benoite Vaux (Diocèse de Verdun) - Chevreux, Jean Baptiste (Impr. de J.B. Laurent, 1863)
Keywords: benoite-vaux

A kis-bényi román izlésű egyház - Henszlmann, Imre (Archaeologiai Közlemények, 1863)
Keywords: bíňa

Lavendon Abbey - Hulton, C.G. (Records of Buckinghamshire or Papers and Notes on the History, Antiquities and Architecture of the County, 1863)
Keywords: lavendon

Shap Abbey and Lord Robert de Clifford - Nicholson, Cornelius (Westmorland Gazette, 1862)
Keywords: shap

Shap Abbey (Westmorland Gazette, 1862)
Keywords: shap

Saint-Laurent (Chronique de Jersey, 1862)
Keywords: st. lawrence

Doksany, býv. královský panenský klášter premonstrátek nad Ohří - Beneš, František (Památky archeologické, 1862)
Keywords: doksany

Zur Geschichte der Abtei Steinfeld - Braun, J. (Annalen des Historischen Vereins für den Niederrhein, 1862)
Keywords: steinfeld

Prieuré d'Athis - Fierville, Charles (Bulletin de la Société des antiquaires de Normandie, 1862)
Keywords: athis

Borne de Juridiction de l'abbaye du Mont Saint-Martin - Gomart, Charles (Etudes Saint-Quentinoises, 1862)
Keywords: mont-saint-martin

Notae Langenses, aus einem Copialbuche des Klosters langen mitgetheilt - Grotefend, C.L. (Zeitschrift des Historischen Vereins für Niedersachsen, 1862)
Keywords: langen

Legende von dem seligen Hermann Joseph - Kaulen, Franz Philip (Verlag von Franz Kirchheim, 1862)
Keywords: 👤 hermann joseph of steinfeld

Der letzte Convent zu S. Georg in Stade. Aus dem Verzeichnis der Bremischen Antoniusgilde - Krause, Karl Ernst Hermann (Archiv des Vereins für Geschichte und Altertümer der Herzogtümer Bremen und Verden, 1862)
Keywords: stade

Notes Archéologiques sur le Mont St. Martin - Prioux, Stanislas (Bulletin de la Société archéologique, historique et scientifique de Soissons, 1862)
Keywords: mont-saint-martin

Auszüge aus dem Kopialbuch des Klosters Griffen (Regesten 1250-1500) - Schroll, Beda (Carinthia: Zeitschrift für Vaterlandskunde, Belehrung und Unterhaltung, 1862)
Keywords: griffen

Das Kloster Rüti. Stiftung der Freiherren von Regensberg und Grabstätte der Grafen von Toggenburg - Vögelin, Anton Salomon (Mitteilungen der Antiquarischen Gesellschaft in Zürich, 1862)
Keywords: rüti

Alnwick Castle - Bede, Cuthbert (Once a Week, 1861)
Keywords: alnwick

Eine Gränzstreitigkeit und Sühne zwischen Kloster Churwalden und Obervatz (Anzeiger für Schweizerische Geschichte und Altertumskunde, 1861)
Keywords: churwalden

Zur Geschichte der Abtei Steinfeld - Braun, J. (Annalen des Historischen Vereins für den Niederrhein, 1861)
Keywords: steinfeld

Notice historique sur l'abbaye de Séry, au diocèse d'Amiens - Darsy, François Irénée (Mémoires de la Société des Antiquaires de Picardie, 1861)
Keywords: séry

A Mortuary Roll sent forth by the Premonstratensian Abbey of West Dereham, Norfolk - Dashwood, George H. (Proceedings of the Society of Antiquaries of London, 1861)
Keywords: west dereham

Chronica de fundaçao do moesterio de Sao Vicente de Lixboa, pello invictissimo e christianissimo dom Alfonso Henriquez 1o rei de Portugal, e como tomou a dita çirade aos Mouros (1108) - Herculano, Alexandre (Portugaliae Monumenta Historica. Scriptores, 1861)
Keywords: lisbon

Magyar Regesták a szepesi káptalan, jászai s leleszi konventek, Kassa és Sopron városok, s több magánosok levéltáraiból s gyűjteményeiből, 1228—1643 - Horváth, Mihály (Magyar Történelmi Tár, 1861)
Keywords: jasov; leles

Sur l'église de Mondaye - Lavalley-Duperroux (Bulletin de la Société des antiquaires de Normandie, 1861)
Keywords: mondaye

Kuzemer - Naarding, J. (Driemaandelijkse bladen, 1861)
Keywords: kuzemer

Rentale de Cokersand: being the bursar's rent roll of the abbey of Cokersand, in the county palatine of Lancaster, for the year 1501 - Raines, F.R. (Printed for the Chetham Society, 1861)
Keywords: cockersand

Indice de los documentos del monasterio de Santa María de Brazacorta - Real Academia de la Historia (Indice de los documentos procedentes de los monasterios y conventos suprimidos que se conservan en el archivo de la Real academia de la historia, 1861)
Keywords: brazacorta

Indice de los documentos del monasterio de Santa María de Fresnillo - Real Academia de la Historia (Indice de los documentos procedentes de los monasterios y conventos suprimidos que se conservan en el archivo de la Real academia de la historia, 1861)
Keywords: fresnillo

Indice de los documentos del monasterio de Santa María de La Vid - Real Academia de la Historia (Indice de los documentos procedentes de los monasterios y conventos suprimidos que se conservan en el archivo de la Real academia de la historia, 1861)
Keywords: la vid

Hermann der Prämonstratenser oder die Juden und die Kirche des Mittelalters - Weber, Ferdinand Wilhelm (Beck, 1861)
Keywords: 👤 hermann joseph of steinfeld

Shap Abbey, Westmorland - Simpson, James (Westmorland Gazette, 1860)
Keywords: shap

Recherches historiques sur l'influence du Protestantisme dans la province d'Auch: Procès-verbal de l'état des églises du diocèse d'Aire au XVIe siècle (suite): Lacqui (Bulletin du Comité d'histoire et d'archéologie de la province ecclésiastique d'Auch, 1860)
Keywords: lacquy

Lebensbeschreibung des gottseligen Jünglings Wilhelm Eiselin, gebornen Bürgersohnes von Mindelheim, und Ordensbruder des Prämonstratenser-Klosters Roth bei Memmingen - Adlgasser, G. (A. Fackler, 1860)
Keywords: rot an der rot

Zur Geschichte der Abtei Steinfeld - Braun, J. (Annalen des Historischen Vereins für den Niederrhein, 1860)
Keywords: steinfeld

Le Prieuré de la Grange de Durance, monument du diocèse d'Agen, dans les Landes de Gascogne - Dardy, Léopold (Impr. de Vve J. Dupuy, 1860)
Keywords: durance

Kurze Geschichte des Königlichen Prämonstratenser-Jungfrauen-Stiftes Doxan : bei Leitmeritz in Böhmen, von seiner Gründung bis zu seiner Aufhebung, nebst Beschreibung der Stiftskirche, ihrer Merkwürdigkeiten in der Vergangenheit und Gegenwart - Feyfar, Mathias Maria (B.G. Teubner, 1860)
Keywords: doksany

L'abbaye de Goujon - Fons, Victor (Mémoires de la Société Archéologique du Midi de la France, 1860)
Keywords: goujon

Beiträge zur Schlägler Chronik, gesammelt und chronologisch geordnet - Markus, Jordan Cajetan (Weidinger, 1860)
Keywords: schlägl

Güterverzeichniß des Klosters Oelinghausen, 1280 - Seibertz, Johann Suibert (Quellen der westfälischen Geschichte, 1860)
Keywords: oelinghausen

La grange de Durance - Villiet, Joseph (Actes de l'Académie nationale des sciences, belles-lettres et arts de Bordeaux, 1860)
Keywords: durance

Fonts de Saint-Just-en-Chaussée (Oise) - Barraud (Mémoires de la Société Académique d'Archéologie, Sciences et Arts du Département de l’Oise, 1859)
Keywords: saint-just-en-chaussée

Das Kloster Gerlachsheim - Bauer, Hermann (Historischer Verein für Württembergisch Franken: Zeitschrift des Historischen Vereins für das Württembergische Franken, 1859)
Keywords: gerlachsheim

Sur Preny et l'abbaye de Sainte-Marie-aux-Bois - Bouteiller, E. de (Bulletin de la Société d'archéologie et d'histoire de la Moselle, 1859)
Keywords: sainte-marie-au-bois

Das adelige Fräuleinstift zu Heinsberg - Braun (Annalen des Historischen Vereins für den Niederrhein, 1859)
Keywords: heinsberg

A Plan of Wendling Abbey - Bulwer, J. (Norfolk Archaeology, 1859)
Keywords: wendling

Inscriptions de l'abbaye de S. Michel - Génard, P. (Inscriptions funéraires et monumentales de la province d'Anvers : arrondissement d'Anvers = Verzameling der graf- en gedenkschriften van de provincie Antwerpen : Arrondissement Antwerpen. Anvers, abbayes et couvents = Antwerpen, abdyen en kloosters, 1859)
Keywords: antwerp

Verhandeling over St.-Michielsabdy te Antwerpen - Génard, P. (Inscriptions funéraires et monumentales de la province d'Anvers : arrondissement d'Anvers = Verzameling der graf- en gedenkschriften van de provincie Antwerpen : Arrondissement Antwerpen. Anvers, abbayes et couvents = Antwerpen, abdyen en kloosters, 1859)
Keywords: antwerp

The Church of Guyzance - Longstaffe, W.H. (Archaeologia Aeliana, 1859)
Keywords: guyzance

Bellelay: traditions, monuments et histoire - Mandelert, P. (Imprimerie et lithographie de Victor Michel, 1859)
Keywords: bellelay

Zur Geschichte der Abtei Knechtsteden - Mooren, Josef Hubert (Annalen des Historischen Vereins für den Niederrhein, 1859)
Keywords: knechtsteden

Abbaye de Val-Chrétien - Pécheur (Bulletin de la Société archéologique, historique et scientifique de Soissons, 1859)
Keywords: val-chrétien

Monographie de l'ancienne abbaye royale Saint-Yved de Braine - Prioux, Stanislas (Didron, 1859)
Keywords: braine

Notice sur la chasuble des miracles, donnée à l'église de Braine - Prioux, Stanislas; Herbelin, Matthieu (Bulletin de la Société académique de Laon, 1859)
Keywords: braine

Abriß der Geschichte des Klosters Czarnowanz - Wattenbach, Wilhelm (Zeitschrift des Vereins für Geschichte und Alterthum Schlesiens, 1859)
Keywords: czarnowąsy

Abbaye de Neufontaines - Boudant (Bulletin de la Société d'Émulation du département de l'Allier, 1858)
Keywords: neuffontaines

Das Prämonstratenserkloster Altenberg bei Wetzlar - Herschel, Karl Adolf (Anzeiger für Kunde der deutschen Vorzeit, 1858)
Keywords: altenberg

Mémoire sur les archives du monastère de Château-l'Abbaye - Le Glay, André Joseph Ghislain (E. Prignet, 1858)
Keywords: château-l'abbaye

Bemerkungen zum Nekrologium von Weißenau - Mooyer, Ernst Friedrich (Zeitschrift für die Geschichte des Oberrheins, 1858)
Keywords: weissenau

Margit-Sziget története - Radványi, Imre (Nyomatott Beimel J. és Kozma Vazulnal, 1858)
Keywords: nyulakszigete

Recherches historiques sur l'ancienne abbaye de Parc - Raymaekers, F.J. (Revue catholique: Recueil Religieux, Philosophique, Scientifique, Historique et Littéraire, 1858)
Keywords: park

Geschichte des Klosters Germerode nach urkundlichen Quellen - Schmincke, Julius Ludwig Christian (Zeitschrift des Vereins für Hessische Geschichte und Landeskunde, 1858)
Keywords: germerode

Necrologium Monasterii Heilissemensis - Van Even, Edward (Vaderlandsch museum voor Nederduitsche letterkunde, oudheid en geschiedenis, 1858)
Keywords: heylissem

Das Prämonstratenser Kloster auf der Insel Usedom von seiner Gründung um das Jahr 1150 bis zu seiner Aufhebung im Jahre 1535 - Zietlow, Eduard Georg Heinrich (W. Dietze, 1858)
Keywords: grobe

Die Kirchenruine von Zsambek in Ungarn - Weiß, Karl (Mittheilungen der K.K. Central-Commission für Erforschung und Erhaltung der Kunst- und Historischen Denkmale, 1857)
Keywords: zsámbék

Die Stiftskirchen zu Griffen und Oberndorf in Kärnthen - Ankershofen, J. von (Mittheilungen der K.K. Central-Commission für Erforschung und Erhaltung der Kunst- und Historischen Denkmale, 1857)
Keywords: griffen; oberndorf

Das Prämonstratenser Mönchskloster Steinfeld in der Eifel. Ein Beitrag zur Specialgeschichte der Preußischen Rheinlande, nebst einem Anhange, enthaltend Nachrichten über einige Kloster des Prämonstratenser- Ordens - Bärsch, Georg (Braselmann, 1857)
Keywords: steinfeld

Vie de Saint-Norbert, fondateur de l'ordre de Prémontré - Bernard (Actes de la Société Jurassienne d'émulation, 1857)
Keywords: 👤 norbert of xanten

Sceau de l'abbaye de Leffe - Borgnet, Jules (Annales de la Société archéologique de Namur, 1857)
Keywords: leffe

Nachrichten über Klöster des Prämonstratenser-Ordens, besonders im Rheinlande und Westphalen - Braun, J.W.J. (Annalen des Historischen Vereins für den Niederrhein, 1857)
Keywords: 🇩🇪 germany (general)

The Premonstratensian Abbey of Bayham; with Some Particulars Relating to its Origin and History - Cooper, George Miles (Sussex Archaeological Collections, 1857)
Keywords: bayham

Quelques mots sur l'ancienne abbaye de Licques - Courtois, Henry (Bulletin historique trimestriel de la Société académique des antiquaires de la Morinie, 1857)
Keywords: licques

L'abbaye de Sainte-Marie-au-Bois - Digot, Auguste (Bulletin de la Société d'archéologie lorraine, 1857)
Keywords: sainte-marie-au-bois

Nekrologium von Weißenau - Mone, Franz Joseph (Zeitschrift für die Geschichte des Oberrheins, 1857)
Keywords: weissenau

Matthieu Herbelin, religieux prémontré - Prioux, Stanislas (A. Morel, 1857)
Keywords: 📚 premonstratensian (general)

Notice historique sur l'abbaye de Bellelay - Quiquerez, Auguste (Actes de la Société Jurassienne d'émulation, 1857)
Keywords: bellelay

L'Abbaye de Beauport - Ramé, Alfred (Bulletin archéologique de l'Association bretonne, 1857)
Keywords: beauport

Urbář kláštera Strahovského složený roku 1410 - Tomek, Václav Vladivoj (Památky archaeologické a místopisné, 1857)
Keywords: strahov

Lotgevallen van Heer Fulco en de Abdij van Bern - Van Dam Van Brakel, W. (1857)
Keywords: berne

Urkunden des Klosters Czarnowanz - Wattenbach, Wilhelm (Codex diplomaticus Silesiae, 1857)
Keywords: czarnowąsy

Nachrichten über Klöster des Prämonstratenser-Ordens, besonders im Rheinlande und Westphalen (Schluß) - Bärsch, G. (Annalen des Historischen Vereins für den Niederrhein, 1856)
Keywords: 🇩🇪 germany (general)

L'Abbaye de Notre-Dame de Beauport, et Suite chronologique des abbés de Beauport - Barthélemy, Anatole (Mélanges historiques et archéologiques sur la Bretagne, 1856)
Keywords: beauport

Památky kláštera želivského - Bezděka, Victor (Památky archéologicke a mistopisne, 1856)
Keywords: želiv

Dureford Abbey, its Fortunes and Misfortunes, with some particulars of the Premonstratensian Orde - Blaauw, W.H. (Sussex Archæological Collections, 1856)
Keywords: durford

Observations sur le cartulaire de Prémontré (XIIIe siècle) - Darras, Joseph Épiphane (Bulletin de la Société archéologique et scientifique de Soissons, 1856)
Keywords: prémontré

Histoire de Rengéval - Dumont, Charles Emmanuel (Histoire des fiefs et principaux villages de la seigneurie de Commercy, comprenant Pont-sur-Meuse, Lérouville, Euville, Vignot et l'abbaye de Rengéval, 1856)
Keywords: rangéval

Zur Geschichte des Klosters Wirberg - Glaser, Karl (Schulprogramm Giessen, 1856)
Keywords: wirberg

Dragsmarks kloster och sagan om Axel och Valborg - Holmberg, Axel Emanue (s.n., 1856)
Keywords: dragsmark

Gründung der prämonstratenser abtei Tepl in Böhmen nach urkunden, legenden und sagen erzählt - Karlik, Hugo (Goedsche'sche Verlagsbuchhandlung, 1856)
Keywords: teplá

Die vormalige Abtei Oberzell - Kestler, Johann Baptist (Archiv des Historischen Vereins für Unterfranken und Aschaffenburg, 1856)
Keywords: oberzell

Historische Daten über das alte Prämonstratenserkloster Windberg - Kornmüller, Joseph (Verhandlungen des Historischen Vereins für Niederbayern, 1856)
Keywords: windberg

Promenade archéologique dans les environs de Soissons. Rapport fait à la Société historique, archéologique et scientifique de Soissons sur les églises, châteaux et abbayes d'Amblegny, Laversine, Coeuvres, Valsery et Longpont - Poquet, Alexandre (V. Didron, 1856)
Keywords: valsery

Das Prämonstratenser-Mönchs-Kloster Leitzkau - Riedel, Adolph Friedrich (Codex Diplomaticus Brandenburgensis, 1856)
Keywords: leitzkau

Necrolog des Klosters Czarnowanz - Wattenbach, Wilhelm (Zeitschrift des Vereins für Geschichte und Alterthum Schlesiens, 1856)
Keywords: czarnowąsy

Nachrichten über Klöster des Prämonstratenser-Ordens, besonders im Rheinlande und Westphalen - Bärsch, G. (Annalen des Historischen Vereins für den Niederrhein, 1855)
Keywords: 🇩🇪 germany (general)

Fondation de l'abbaye de Humilimont ou de Marsens - Dey, J. (Mémorial de Fribourg, 1855)
Keywords: humilimont

The Hospital of St. Leonard in the Parish of Alnwick - Dickson, W.M. (Archaeologia Aeliana, 1855)
Keywords: st. leonard's hospital

Die lateinischen und deutschen Lebensbeschreiber Ludwigs, des letzten Grafen von Arnstein - Friedemann, Friedrich Traugott (Annalen des Vereins für Nassauische Altertumskunde und Geschichtsforschung, 1855)
Keywords: arnstein

Nachtrag zur Geschichte des Frauenklosters Unterzell - Kestler, Johann Baptist (Archiv des Historischen Vereins für Unterfranken und Aschaffenburg, 1855)
Keywords: unterzell

Über die Kirche, den Hochaltar und das Kloster zu Rehna - Lisch, Georg Christian Friedrich; Masch, Gottlieb Matthias Carl (Jahrbücher des Vereins für Mecklenburgische Geschichte und Altertumskunde, 1855)
Keywords: rehna

Über einige mittelalterliche Kunstdenkmäler von Breslau: die alte Burg von Breslau, die Martinikirche, die heilige Kreuz-Kirche, die ehemaligen Kirchen zu St. Vincenz, St. Michaelis und Allerheiligen auf dem Elbing, und deren Reste ; eine historisch-artistische Abhandlung - Luchs, Hermann (1855)
Keywords: wrocław

Notice sur l’abbaye de Valsery - Poquet, Alexandre (Bulletin de la Société historique et archéologique de Soissons, 1855)
Keywords: valsery

Notices sur les couvents du diocèse de Lausanne: Prémontrés et Prémontrées - Schmitt, M. (Mémorial de Fribourg, 1855)
Keywords: 🇨🇭switzerland (general)

Abdruck und Erläuterung verschiedener Urkunden. IX. Stiftungsbrief über das Kloster zur Himmelspforte in Wilen bei Basel, von 1303 - Bader (Zeitschrift für die Geschichte des Oberrheins, 1854)
Keywords: himmelspforte (germany)

Real ex-monasterio de Santa María de Bugedo - Salomon, Remigio (Semanario Pintoresco Español, 1854)
Keywords: bujedo de candepajares

De Anselmo: Episcopo Havelbergensi, postea Archiepiscopo Ravennate - Strerath, Jakob (1854)
Keywords: 👤 anselm of havelberg

Notice sur quelques sceaux inédits - Barthélemy, Anatole de (Révue archéologique, 1853)
Keywords: beauport

Urbarium der Chorherren und des Domcapitels zu Chur unter S. Luziensteig, nach dessen Erneuerung von 1 mai 1393 - Bergmann, J. (Denkschriften der Akademie der Wissenschaften, 1853)
Keywords: chur (st luzi)

Histoire des Monastères de l'Étanche et de Benoite-Vaux (Rectifications et additions à l'Histoire des Monastères de l'Étanche, etc.) - Dumont, Charles Emmanuel (Imprimerie de Dard, 1853)
Keywords: benoite-vaux; l'étanche

Kirche des Klosters St. Wiperti zu Quedlinburg - Hartmann, A. (Zeitschrift für Bauwesen, 1853)
Keywords: quedlinburg

Das Kloster Zuckau im dreizehnten und vierzehnten Jahrhundert - Hirsch, Theodor (Neue preußische Provinzial-Blätter, 1853)
Keywords: żukowo

Necrologium Bellelagiense - Nicolet, Célestin (V. Michel, 1853)
Keywords: bellelay

On Easby Abbey - Raine, James (Associated Architectural Societies Reports and Papers, 1853)
Keywords: easby

Beschreibung und Geschichte der Schlosskirche zu Quedlinburg und der in ihr vorhandenen Alterthümer. Nebst Nachrichten über die St. Wipertikirche bei Quedlinburg, die Kirche zu Kloster Groningen, die Schlosskirche zu Gernrode, die Kirchen zu Frose, Drübeck, Huyseburg, Conradsburg, etc. - Ranke, E.F.; Kugler, F. (Kleine Schriften zur Kunstgeschichte. Mit Illustrationen und andern artistischen Beilagen, 1853)
Keywords: quedlinburg

Researches into the History of the Abbey of Otteham - Cooper, George Miles (Sussex Archaeological Collections, 1852)
Keywords: otteham

Urkunden-Archiv des Klosters Bebenhausen vom XII. und XIII. Jahrhundert - Dambacher, Joseph (Zeitschrift für die Geschichte des Oberrheins, 1852)
Keywords: bebenhausen

Notice sur l'abbaye de Silly - Gravelle-Desulis, Pierre Jacques (Impr. de Vve Poulet-Malassis, 1852)
Keywords: silly

Notice sur les abbayes d’Estival, Moyenmoutier et Senones et trois manuscrits de la Bibliothèque de Saint-Dié - Matter, J. (Revue d'Alsace, 1852)
Keywords: étival

Necrologium Bellelagiense - Nicolet, Célestin (Coup d'œil sur les travaux de la société jurassienne, 1852)
Keywords: bellelay

Wloski klasztoru norbertanskiego w Nowym Saczu obdarzone prawem swieckiem - Sartyni, Mateusz Eustachy (Dodatek tygodniowy do Gazety Lwowskiej, 1851)
Keywords: nowy sącz

Hospices de Corneux et de Theuley - Besson, Louis (Histoire de la ville de Gray et de ses monuments, 1851)
Keywords: gray

Notice sur l'église prieurale de Blanzey - Digot, Auguste (Bulletin de la Société d'archéologie lorraine, 1851)
Keywords: blanzey

Das Leben des Grafen Godfried von Kappenberg und seine Klosterstiftung - Geisberg, Caspar (Westfälische Zeitschrift - Zeitschrift für vaterländische Geschichte und Altertumskunde, 1851)
Keywords: cappenberg

On Precatory or Mortuary Rolls, and Particularly One of the Abbey of West Dereham, Norfolk - Nichols, John Gough (Memoirs illustrative of the history and antiquities of Norfolk and the city of Norwich, communicated to the annual meeting of the Archaeological institute of Great Britain and Ireland, held at Norwich, July, 1847, with a general report of the proceedings of the meeting, and a catalogue of the museum formed on that occasion, 1851)
Keywords: west dereham

Zur Charakteristik des älteren Ziegelbaues in der Mark Brandenburg mit besonderer Rücksicht auf die Klosterkirche zu Jerichow - Quast, Ferdinand von (Deutsches Kunstblatt: Zeitschrift für bildende Kunst, Baukunst und Kunsthandwerk, 1850)
Keywords: jerichow

Das Kloster Allerheiligen im Schwarzwalde (Der Katholik, 1850)
Keywords: allerheiligen

Johannes van der Goes, 21ste Abt van het Maria-Klooster te Middelburg. Eene bijdrage tot de 700jarige geschidenis van dat Klloster - Ab Utrecht Dresselhuis, Johannes (Nehalennia: jaarboekje voor zeeuwsche geschiedenis en letteren, 1850)
Keywords: middelburg

Ane breve cronicle of the Earlis of Ross: including notices of the Abbots of Fearn, and of the family of Ross of Balnagown - Baillie, W.R. (T. Constable, 1850)
Keywords: fearn

Charte de 1224 - Barthélemy, Anatole (Bulletin du Comité historique des monuments écrits de l'histoire de France, 1850)
Keywords: beauport

Dénombrement des titres concernant l'abbaye de Prémontré - Deviolaine, A. (Bulletin de la Société archéologique de Soissons, 1850)
Keywords: prémontré

Das Cisterzienser-Kloster zu Dobrilugk verkauft dem Prämonstratenser-Stifte auf dem Marienberge bei der Altstadt Brandenburg eine Anzahl Bücher. 1441. Nach dem Original im Geheimen Archive zu Berlin mitgetheilt - Heffter, M. W. (Serapeum. Zeitschrift für bibliothekwissenschaft, handschriftenkunde und ältere litteratur, 1850)
Keywords: brandenburg:st marien

Über die Kirche und das Kloster zu Rehna - Lisch, Georg Christian Friedrich (Jahrbücher des Vereins für Mecklenburgische Geschichte und Altertumskunde, 1850)
Keywords: rehna

Verzeichnis der Nonnen des Klosters Rehna um das Jahr 1500 - Lisch, Georg Christian Friedrich (Jahrbücher des Vereins für Mecklenburgische Geschichte und Altertumskunde, 1850)
Keywords: rehna

Verzeichnis der Pröpste und Priorinnen des Klosters Rehna - Lisch, Georg Christian Friedrich (Jahrbücher des Vereins für Mecklenburgische Geschichte und Altertumskunde, 1850)
Keywords: rehna

Notice sur l'abbaye de Bucilly - Piette, Amédée (Papillon, 1850)
Keywords: bucilly

Presentation and translation of a deed concerning land in Scarisbrick granted to Cockersand Abbey - Smith, James (Transactions of the Historic Society of Lancashire and Cheshire, 1850)
Keywords: cockersand

Historia del monasterio de canónigos Premonstratenses de Bellpuig de las Avellanas: su fundacion: muerte violenta de su fundador y su sepultura en este monasterio: noticia de tres individuos literatos y célebres anticuarios del mismo y catálogo de sus abades - Villanueva, Jaime (Historia del monasterio de canonigos Premonstratenses de Bellpuig de las Avellanas, 1850)
Keywords: bellpuig de las avellanes

Beiträge zur Geschichte des Klosters Brunnenburg - Vogel, C.D. (Nassauische Annalen, 1850)
Keywords: brunnenburg

Beauchief Abbey (Sheffield and Rotherham Independent, 1849)
Keywords: beauchief

Abbaye de Beauport - Barthélemy, Anatole de (Bulletin monumental, 1849)
Keywords: beauport

Geschichtsabriß des vormaligen Frauenklosters Unterzell - Kestler, Johann Baptist (Archiv des Historischen Vereins für Unterfranken und Aschaffenburg, 1849)
Keywords: unterzell

Urkunden des Prämonstratenser Stiftes Geras, zusammengestel und erlaütert (1188-1416) - Mayer, Theodor (Archiv für Kunde Österreichischer Geschichts-Quellen, 1849)
Keywords: geras

Notice sur la Grange-aux-Dames et origine du mot Queuleu, nom d'une commune près de Metz - Munier, François (Mémoires de l'Académie nationale de Metz, 1849)
Keywords: grange-aux-dames

Chronicon et Cartularium Abbatiae Sancti Nicolai Furnensis, ordinis Premonstratensis, et Chronicon Bethaniae seu Domus S. Joseph Furnensis - Putte, Ferdinand van de; Carton, Charles Louis (Recueil de chroniques, chartes et autres documents concernant l'histoire et les antiquités de la Flandre-Occidentale, 1849)
Keywords: bethania; veurne

Notice historique sur l'ancienne abbaye d'Averboden - Wolters, Mathias Joseph (F. et E. Gyselynck, 1849)
Keywords: averbode

Archiv des Klosters Heiligenberg - Hodenberg, Wilhelm von (Hoyer Urkundenbuch, 1848)
Keywords: heiligenberg

Histoire de la Ville et des Sires de Coucy-le-Chateau suivie d'une notice historique sur Anizy, Marle, Vervins, La Fère, St-Gobain, Pinon, Folembray, Saint-Lambert, et sur les anciennes abbayes de Nogent et de Prémontré - Melleville, Maximilien (Bureau du Journal de l'Aisne, 1848)
Keywords: prémontré

De Abdij van Mariënweerd en het Klooster te Zennewynen - Römer, R.C.H. (Nederlandsch archief voor kerkelijke geschiedenis, 1848)
Keywords: mariënweerd; zennewijnen

San Cristobal de Ibeas - Assas, Manuel de (Semanario pintoresco español, 1847)
Keywords: ibeas

Notice abrégée sur les archives de l'ancienne abbaye de Château, près de Mortagne (Nord) (analyse de charles , 1155-1299) - Bénézech de Saint-Honoré, Joseph Marie Georges (Bulletin de la Commission historique du département du Nord, 1847)
Keywords: château-l'abbaye

Note sur un billet d'indulgence délivré au XIIIe siècle par l'abbaye d'Ardennes, près Caen, à ses bienfaiteurs - Charma, Antoine (Mémoires de la Société des Antiquaires de Normandie, 1847)
Keywords: ardenne

Notice historique sur l'ancienne abbaye de Bellosanne - Cochet, Jean-Benoît-Désiré (Précis analytique des travaux de l'académie des sciences, belles-lettres et arts de Rouen, 1847)
Keywords: bellozanne

Notice sur un ancien temple ou crypte dont la découverte a été faite sous le pavement de l'ancienne église de l'abbaye de St-Michel à Anvers, au mois de mai 1843 - Mertens, F.H. (Annales de l'Académie royale d'Archéologie, 1847)
Keywords: antwerp

Notice sur l'Isle-Dieu - Sainte-Hermienne, H. de (Annales de la Société royale académique de Nantes et du département de la Loire-Inférieure, 1847)
Keywords: isle-dieu

Liber S. Marie de Dryburgh, Registrum Cartarum Abbacie Premonstratensis de Dryburgh - Spottiswood, John (Bannatyne Club Publications, 1847)
Keywords: dryburgh

St. Leonard's Hospital at Alnwick, Northumberland - Dugdale, William (Monasticon Anglicanum: a History of the Abbies and other Monasteries, Hospitals, Frieries, and Cathedral and Collegiate Churches, with their Dependencies, in England and Wales, 1846)
Keywords: st. leonard's hospital

Histoire de Braine et de ses environs - Prioux, Stanislas (Dumoulin, 1846)
Keywords: braine

Notizen zur Geschichte des Klosters Sulz - Schumacher, Karl (Jahresbericht des Historischen Vereins für Mittelfranken, 1846)
Keywords: sulz

Corton - Suckling, Alfred (The History and Antiquities of the County of Suffolk, 1846)
Keywords: corton

Les Ruines lorraines, chroniques monumentales I: Sainte-Marie-Aux-Bois (Meurthe) - Civry, Victor de (Vagner, 1845)
Keywords: sainte-marie-au-bois

Die Stiftung des Klosters Rehna - Lisch, Georg Christian Friedrich (Mecklenburgische Jahrbücher, 1845)
Keywords: rehna

De Abdij van Mariënweerd - Römer, R.C.H. (Nederlandsch archief voor kerkelijke geschiedenis, 1845)
Keywords: mariënweerd

Zur kunde Alternorddeutscher Klosterbibliotheken inbesondern des Klosters Leitzkau in XII und XIII Jahrhundert - Schönemann, C.P.C. (Serapeum: Zeitschrift für Bibliothekwissenschaft, Handschriftenkunde und ältere Literatur, 1845)
Keywords: leitzkau

Cronica Monasterij de Alnewyke et quodam Libro Cronicanum in Libraria Collegij Regalis Cantabrigiae de dono Regis Henrici VI Fundatoris - Dickson, W. (Archaeologia Aeliana, 1844)
Keywords: alnwick

Notice relative to the Hospital of St. Leonard in the Parish of Alnwick - Dickson, W.M. (Archaeologia Aeliana, 1844)
Keywords: st. leonard's hospital

Monumenta rerum ilfeldensium; ex schedis suis collegit et additis Leuckfeldianis - Foerstemann, Ernst Günther (1843)
Keywords: ilfeld

Zur Geschichte des Klosters und Gymnasiums zu Arnsberg - Hoegg, Franz Xaver (Zur zweiten Säcularfeier des Königlichen Laurentianums zu Arnsberg, 1843)
Keywords: wedinghausen

Das Dom-Collegiat-Stift zu Broda - Lisch, Georg Christian Friedrich (Jahrbücher des Vereins für Mecklenburgische Geschichte und Altertumskunde, 1843)
Keywords: broda

Fontaine-André, son ordre, sa règle, ses nécrologes - Matile, George-Auguste (Musée Historique de Neuchatel et Valangin, 1843)
Keywords: fontaine-andré

Über das ehemalige Kloster Pöhlde - Nolte, Hermann (Hannoverisches Magazin, 1843)
Keywords: pöhlde

Note sur l'abbaye d'Ardenne - Caumont, Arcisse de (Bulletin Monumental, 1842)
Keywords: ardenne

Kurze Geschichte des vormaligen Klosters Tiefenthal im Rheingau - Dahl, C. (Nassauische Annalen: Jahrbuch des Vereins für Nassauische Altertumskunde und Geschichtsforschung, 1842)
Keywords: tiefenthal

Een zegbrief of arbitragie van den abt van Drongen, van het jaer 1360 - Duyse, Prudens van (Belgisch museum voor de Nederduitsche tael- en letterkunde en de geschiedenis des vaderlands, 1842)
Keywords: drongen

Annales de l'Abbaye du Lac-de-Joux: depuis sa fondation jusqu'à sa suppression en 1536 - Gingins-La-Sarra, Frédéric Jean Charles de (Imprimerie-Librairie de Marc Ducloux, 1842)
Keywords: lac de joux

Geschichte der Habits-Veränderungen des Rigischen Domcapitels, nebst Unter suchungen über streitige Gegenstände in derselben, mit urkundlichen Beilagen - Kallmayer, Theodor (Mittheilungen aus dem Gebiete der Geschichte Liv-, Ehst- und Kurland's ; herausgegeben von der Gesellschaft für Geschichte und Alterthumskunde der russischen Ostsee-Provinzen, 1842)
Keywords: rīga

Erläuterungen zu dem Totenbuche des Klosters Heinsberg - Mooyer, Ernst Friedrich (Westfälische Zeitschrift - Zeitschrift für vaterländische Geschichte und Altertumskunde, 1842)
Keywords: heinsberg

Fragmenta necrologii monasterii Hinsbergensis - Quix, Charles (Westfälische Zeitschrift - Zeitschrift für vaterländische Geschichte und Altertumskunde, 1842)
Keywords: heinsberg

Bischof Ludolph von Ratzeburg (Jahrbücher des Vereins für Mecklenburgische Geschichte und Altertumskunde, 1841)
Keywords: 👤 ludolf of ratzeburg

Melrose and Its Vicinity: Being an Account of Such Objects of Historical and Classical Interest as are to be Found in Its Neighbourhood, with a History and Description of the Abbeys of Melrose, Dryburgh, Kelso and Jedburgh, with a Particular Account of Abbotsford - Deans, William (J.B. Mould, 1841)
Keywords: dryburgh

Notice sur la Chapelle de Sainte-Magdeleine située à la commune d'Ustaritz - Duvoisin, C. (Bulletin de la Société des sciences, lettres et arts de Pau, 1841)
Keywords: otsantz

Notice sur l'abbaye de Belle-Étoile, arrondissement de Domfront, département de l'Orne - Hurel, Julien-Modeste (Impr. de Levavasseur, 1841)
Keywords: belle-étoile

Notice historique sur l'abbaye de St.-Josse ou Dommartin - Parenty, François Joseph (Le Puits Artésien, Revue du Pas de Calais, 1841)
Keywords: dommartin

Notice sur l'abbaye de Clairfontaine - Piette, Amédée (Papillon, 1841)
Keywords: clairfontaine

Nachricht von der Auffindung einer Anzahl alter Handschriften des ehemaligen Domcapitels zu Havelberg - Riedel, Adolph Friedrich (Serapeum: Zeitschrift für bibliothekwissenschaft, handschriftenkunde und ältere litteratur, 1840)
Keywords: havelberg

Das ehemalige Prämonstratenser-Chorfrauen-Stift Chotieschau im Pilsner Kreise Böhmens: Aus Tepler u. Chotieschauer Archivschriften - Köpl, Robert Christoph (Thabor, 1840)
Keywords: chotěšov

Beknopte oudheidkundige verhandeling over het klooster Kusemer - Rijkens, J.G. (Almanak ter bevordering van kennis en goeden smaak, 1840)
Keywords: kuzemer

Das Leben und Wirken des Bischofs Anselm von Havelberg - Spieker, Christian Wilhelm (1840)
Keywords: 👤 anselm of havelberg

Die Ruinen des Klosters zu Belbog - Temme, Jodocus Donatus Hubertus (Die Volkssagen von Pommern und Rügen, 1840)
Keywords: białoboki

Namen der Dörfer samt allen Pertinentien des Klosters Belbog (Baltische Studien, 1839)
Keywords: białoboki

Zur Geschichte des ehemaligen Klosters Selbold - Calaminus, Anton (Zeitschrift für die Provinz Hanau: zur Aufklärung ihrer Geschichte, ihrer natürl. Beschaffenheit u. ihres Culturstandes, sowie d. diesem entgegenstehenden Hindernisse, 1839)
Keywords: selbold

Origine de la dévotion de Notre-Dame de Sarrance - Lassalle, F. de (1839)
Keywords: sarrance

Series et Gesta Abbatum - Libental, Nicholas (Scriptores rerum silesiacarum oder Sammlung schlesischerer Geschichtschreiber, 1839)
Keywords: wrocław

Geschied- en oudheidkundige beschouwing van Bakkeveen - Meer, D.H. van der (Friesche Volks Almanak, 1839)
Keywords: bakkeveen

Blanchelande, abbaye du diocèse de Coutances, commune de Varenguebec - Richomme, Florent (Annuaire du Département de la Manche, 1839)
Keywords: blanchelande

Het Klooster te Heiligerlee - Zuidema, P. (Groninger Volksalmanak, 1839)
Keywords: heiligerlee

Die Stiftung des Klosters Broda und das Land der Rhedarier - Lisch, Georg Christian Friedrich (Jahrbücher des Vereins für Mecklenburgische Geschichte und Alterthumskunde, 1838)
Keywords: broda

Urkunden des Klosters Broda - Lisch, Georg Christian Friedrich (Jahrbücher des Vereins für Mecklenburgische Geschichte und Alterthumskunde, 1838)
Keywords: broda

Aland - Suur, Hemmo (Geschichte der ehemaligen Klöster in der Provinz Ostfriesland, 1838)
Keywords: aland

Barthe - Suur, Hemmo (Geschichte der ehemaligen Klöster in der Provinz Ostfriesland, 1838)
Keywords: barthe

Langen - Suur, Hemmo (Geschichte der ehemaligen Klöster in der Provinz Ostfriesland, 1838)
Keywords: langen

Palmar - Suur, Hemmo (Geschichte der ehemaligen Klöster in der Provinz Ostfriesland, 1838)
Keywords: palmar

L'abbaye de Blanchelande - Pontaumont, Emile de (Bulletin de l'Académie ébroïcienne, 1837)
Keywords: blanchelande

Descriptio de Origine Conventus, postea Abbatiae Trunchiniensis, ordinis Praemonstratensis; de ejus Fundatore et Loco, et omnibus circumstantiis, cum annotatione temporum, etc. - Smet, Joseph Jean de (Recueil des chroniques de Flandre, 1837)
Keywords: drongen

Easby Abbey, Yorkshire (The Penny magazine of the Society for the Diffusion of Useful Knowledge, 1836)
Keywords: easby

Urkundliche Geschichte der Prämonstratenser und ihrer Äbte zum hl. Vincenz von Breslau - Görlich, Franz Xaver (Josef Max und Komp., 1836)
Keywords: wrocław

Klasztor Norbertanek w Strzelnie - Kothe, J. (Przyjaciel Ludu czyli Tygodnik potrzebnych i pożytecznych wiadomości, 1835)
Keywords: strzelno

Geschichtliche Nachrichten über das Laurentianum zu Wedinghausen bei Arnsberg - Baaden, Philipp Augustin (Jahresbericht über das Königliche Laurentianum zu Arnsberg in dem Schuljahre 1834-1835, 1835)
Keywords: wedinghausen

Essai sur la châtellenie et l'abbaye de Saint-Just-en-Chaussée - L'Escalopier, Charles de (Vve Dondey-Dupré, 1835)
Keywords: saint-just-en-chaussée

Nekrolog der Abtei Engelport - Stramberg, Christian von (Archiv für rheinische Geschichte, 1835)
Keywords: engelport

Zur Geschichte des Klosters und der Stadt Osterhofen - v. R. (Verhandlungen des historischen Vereines in dem Unterdonaukreise, 1835)
Keywords: osterhofen; 📚 premonstratensian (general)

Kurze Geschichte von dem Prämonstratenser-Stift Obermarchtal von seinem Anfange 1171 bis zur seiner Auflösung 1802. Zusammengetragen von einem Mitglied dieses Stiftes - Walter, Friedrich (Feger, 1835)
Keywords: marchtal

Verzeichnis der bei dem Verkaufe des Damenstiftsgutes Osterhofen an den Staat vorgefundenen Urkunden (Verhandlungen des Historischen Vereines in dem Unterdonaukreise, 1834)
Keywords: osterhofen

Zur Geschichte des Klosters und der Stadt Osterhofen (Verhandlungen des Historischen Vereines in dem Unterdonaukreise, 1834)
Keywords: osterhofen

Iron Matrix of the Seal of the Abbey of Langley in Norfolk - Freeling, Francis (Archaeologia, 1834)
Keywords: langley

Abbaye d'Ardennes, de l'Ordre de Saint-Norbert ou des Prémontrés - Léchaudé d'Anisy, Amédée (Mémoires de la Société des antiquaires de Normandie, 1834)
Keywords: ardenne

Abbats [sic] of Tichfield Abbey, in Hampshire - Madden, F. (Collectanea Topographica et Genealogica, 1834)
Keywords: titchfield

Beiträge zur Geschichte des ehemaligen Klosters Vessra - Oesterreicher, Paul (Neue Mittheilungen aus dem Gebiete historisch-antiquarischer Forschungen, 1834)
Keywords: veßra

L'Abbaye de St. Augustin-lez-Thérouanne - Piers, Hector-Beaurepaire (Mémoires de la Société des antiquaires de la Morinie, 1834)
Keywords: saint-augustin-lès-thérouanne

Romeswerf-Rozenkamp nu Nieuwenklooster - Rijkens, J.G. (Almanak ter bevordering van kennis en goeden smaak, 1834)
Keywords: nijenklooster

Das Kloster Belbog bey Treptow an der Rega - Brummer, G.F. (Baltische Studien, 1833)
Keywords: białoboki

Notice sur Serques - Hermand, Alexandre (Mémoires de la Société des antiquaires de la Morinie, 1833)
Keywords: serques

The Monastic Annals of Teviotdale, Or, the History and Antiquities of the Abbeys of Jedburgh, Kelso, Melros and Dryburgh - Morton, James (W.H. Lizars, 1832)
Keywords: dryburgh

Geschichte des Klosters Wedinghausen bei Arnsberg und des dortigen Gymnasiums, Abt. 1: Geschichte des Klosters bis zum Jahre 1368 - Pieler, Franz Ignaz (Jahresbericht über das Laurentianum zu Arnsberg, 1832)
Keywords: wedinghausen

Geschiedkundige verhandeling van het klooster te Wittewierum en dat van Schildwolde - Rijkens, J.G. (Almanak ter bevordering van kennis en goeden smaak, 1832)
Keywords: bloemhof; schildwolde

Urkunden des Klosters Clarholz, die Wahl von Kirchenvögten betreffend - Von Ledebur, Leopold (Allgemeines Archiv für die Geschichtskunde des preußischen Staates, 1830)
Keywords: clarholz

Histoire de Braine depuis son origine jusqu'à présent, de la fondation de l'abbaye de Saint-Yved, des religiuex prémontrés, celle de l'abbaye de Chartreuve, des dames religieuses bénédictines de Notre-Dame, avec la prise de Braine par les ennemis, etc. - Château (1829)
Keywords: braine

Geschichte des vormaligen Reichsstifts und der Stadt Quedlinburg - Fritsch, Johann Heinrich (1828)
Keywords: quedlinburg

Versuch einer topographischen Geschichte der Pfarrei Roggenburg - Weiler, Thomas Ludolph (1828)
Keywords: roggenburg

Documentos inéditos en que se demuestra la existencia de un monasterio premostratense en la diócesis de Vich - Ripoll Vilamajor, Jaume (Por Ignacio Valls impresor de S.M., 1827)
Keywords: fondarella

Einige historische Notizen von dem Kloster Füssenich - Bärsch, Georg (Vaterländische Chronik der kgl. preußischen Rheinprovinzen, 1826)
Keywords: füssenich

Mémoire sur l'église royale de Saint-Ived de Braisne - Beaucamp (Impr. de D. Barbier, 1825)
Keywords: braine

Shap Abbey - Hall, George (Westmorland Gazette, 1824)
Keywords: shap

A descriptive and historical view of Alnwick, the County Town of Northumberland; and of Alnwick Castle, Alnwick and Hulne Abbeys, Brislee Tower, the Borough of Alwnick, etc. - Davison, W. (1822)
Keywords: alnwick

Die Prämonstratenser-Abtey Bruck an der Taya - Gollinger, Joseph (Archiv für Geographie, Historie, Staats- und Kriegskunst, 1822)
Keywords: louka

Die Prämonstratenser-Abtey Bruck an der Taya (Fortsetzung) - Gollinger, Joseph (Archiv für Geographie, Historie, Staats- und Kriegskunst, 1822)
Keywords: louka

Die Prämonstratenser-Abtey Bruck an der Taya (Fortsetzung) - Gollinger, Joseph (Archiv für Geographie, Historie, Staats- und Kriegskunst, 1822)
Keywords: louka

Die Prämonstratenser-Abtey Bruck an der Taya (Fortsetzung) - Gollinger, Joseph (Archiv für Geographie, Historie, Staats- und Kriegskunst, 1822)
Keywords: louka

Die Prämonstratenser-Abtey Bruck an der Taya (Fortsetzung) - Gollinger, Joseph (Archiv für Geographie, Historie, Staats- und Kriegskunst, 1822)
Keywords: louka

Die Prämonstratenser-Abtey Bruck an der Taya (Fortsetzung) - Gollinger, Joseph (Archiv für Geographie, Historie, Staats- und Kriegskunst, 1822)
Keywords: louka

Historical account of Beeleigh Abbey, Essex - Draper, George (G. Draper, 1818)
Keywords: beeleigh

Nachricht von dem Prämonstratenser Frauenstifte zu Kaunicz in Mähren - Dlabacz, Gottfried Johann (Gottlieb Haase, 1817)
Keywords: kounice

Geschichte der Abtei Bredelar - Seibertz, Johann Suibert (Historisch-geographisch-statistisch-literarisches Jahrbuch für Westfalen und den Niederrhein, 1817)
Keywords: bredelar

Cappenberg und Varlar - Raet, Friedrich Wilhelm von (Hermann. Eine Zeitschrift von und für Westfalen oder der Lande zwischen Weser und Maaß, 1815)
Keywords: cappenberg; varlar

The history of Richmond, in the county of York; including a description of the castle, friary, Easeby Abbey, and other remains of antiquity in the neighbourhood - Clarkson, Christopher (T. Bowman at the Albion Press, 1814)
Keywords: easby

Couvent de Weyer (Mercure du Département de la Roer, 1813)
Keywords: cologne (weiher)

Monumenta coenobii S. Salvatoris - Bayerischen Akademie der Wissenschaften (Monumenta Boica, 1813)
Keywords: griesbach

Geschichte des alten adelichen Frauenklosters Sulz - Büttner, Heinrich Christoph (Franconia: Beiträge zur Geschichte, Topographie u. Litteratur von Franken, 1813)
Keywords: sulz

Auszug as dem Schöftlarischen Traditionen-Codex, der am Anfange des XIIIten Jahrhundertes angefertiget worden, und in M.B. VIII. pag. 363 seq. abgedruckt zu lesen ist - Krenner, J. von (Historische Abhandlungen der Königlich-Baierischen Akademie der Wissenschaften, 1813)
Keywords: schäftlarn

Loddon Hundred: Langley Town and Abbey - Blomefield, Francis (An Essay Towards A Topographical History of the County of Norfolk, 1809)
Keywords: langley

Inscriptiones monumentorum in regia ecclesia ordinis Praemonstratensis Pragae in Monte Sion - Dlabacz, Gottfried Johann (1808)
Keywords: strahov

Clackclose Hundred and Half: West-Derham - Blomefield, Francis (An Essay Towards A Topographical History of the County of Norfolk, 1807)
Keywords: west dereham

Historische Darstellung des Ursprungs und der Schicksale des königl. Stiftes Strahow: Zweyte Periode vom J. 1200 - 1586 - Dlabacz, Gottfried Johann (1806)
Keywords: strahov

Historische Darstellung des Ursprungs und der Schicksale des königlichen Stiftes Strahow: Erste Periode - Dlabacz, Gottfried Johann (1805)
Keywords: strahov

Parish of Kettlewell - Whitaker, Thomas Dunham (The history and antiquities of the deanery of Craven, in the county of York, 1805)
Keywords: kettlewell

Diplomatische Nachrichten von dem vormaligen Kloster Gerlachsheim im Taubergrunde - Stumpf, Andreas Sebastian (Denkwürdigkeiten der teutschen, besonders fränkischen Geschichte, 1804)
Keywords: gerlachsheim

Nachrichten von der Prämonstratenser-Abtei Hamborn, der einzigen Herrenabtei im Herzogtum Kleve - Borheck, August Christian (Beiträge zur Erd- und Geschichtskunde der deutschen Niederrheinlande, 1803)
Keywords: hamborn

La-Corzana - Martínez Marina, Francisco (Diccionario Geográfico-histórico de España, 1802)
Keywords: lacorzana

Über das adelige, weltliche Fräulein Stift Elsey in der Grafschaft Hohen-Limburg. Nebst einigen Bemerkungen über die Geschichte, die Verfassung und Kultur der Gegend um dasselbe her, während und nach dem Mittelalters - Möller, Johann Friedrich (1802)
Keywords: elsey

An historical account of Beauchief Abbey, in the county of Derby, from its first foundation to its final dissolution - Pegge, Samuel (John Nichols and Son, 1801)
Keywords: beauchief

Historische Nachrichten von dem adelichen Frauleinstifte Keppel, im Siegenischen - Arnoldi, Johannes von (Geschichte der Oranien-Nassauischen Länder und ihrer Regenten, 1800)
Keywords: keppel